Glass-based articles having a metal oxide concentration gradient
A glass-based article with a non-zero metal oxide concentration gradient and optimized stress distribution addresses the fracture resistance issue in thin glass, enhancing its breakage resistance and fragmenting properties.
Patent Information
- Application Number
- CN202111595635.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-07-25
- Filing Date
- 2017-04-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2037-04-10
AI Technical Summary
Existing glass-based articles, especially those thinner than 3 mm, lack the necessary compressive stress profile to prevent fracture propagation, making them unsuitable for applications requiring thin and lightweight yet crack-resistant materials.
A glass-based article with a non-zero metal oxide concentration gradient varying along its thickness, achieving a maximum central tension greater than 71.5/√(t) and a stress distribution with a tangent line slope greater than 0.1 MPa/μm, resulting in improved fracture resistance.
The glass-based article exhibits enhanced breakage resistance, fracturing into multiple fragments upon impact, with improved compressive stress and central tension profiles, suitable for thin applications.
Smart Images

Figure CN114409250B_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of April 10, 2017, application number 201710230496.5, and name “Glass-based product with metal oxide concentration gradient”.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of and priority under 35 U.S.C. §119 to U.S. Provisional Application Serial No. 62 / 366,338, filed on June 25, 2016, and U.S. Provisional Application Serial No. 62 / 320,077, filed on April 8, 2016, the contents of which are relied upon by this application and are incorporated herein by reference in their entirety. Background Art
[0004] The present invention relates to glass-based articles that exhibit improved damage resistance, including improved fracture resistance, and more particularly to glass and glass-ceramic articles that exhibit a non-zero metal oxide concentration gradient or a concentration that varies along a substantial portion of the thickness.
[0005] Glass-based articles often experience severe impacts that introduce large defects into the surfaces of these articles. These defects can extend from the surface to no more than about 200 micrometers (μm). Typically, thermally tempered glass is used to prevent rejections caused by these defects being introduced into the glass because thermally tempered glass often exhibits a large compressive stress (CS) layer (e.g., about 21% of the total thickness of the glass) that can prevent defects from further propagating into the glass and thereby preventing rejections. An example of a stress distribution resulting from thermal tempering is shown in FIG. 1 . In FIG. 1 , a thermally treated glass article 100 includes a first surface 101 , a thickness t1 , and a surface CS 110 . The CS of the thermally treated glass article 100 decreases along the first surface 101 to a depth of compression (DOC) 130 , as defined herein, at which the stress transitions from compressive stress to tensile stress and reaches a maximum central tension (CT) 120 .
[0006] Currently, thermal tempering is limited to thick glass-based articles (i.e., glass-based articles having a thickness t1 of about 3 mm or more) because, in order to achieve thermal strengthening and the desired residual stress, a sufficient thermal gradient must be formed between the core and the surface of these articles. These thick articles are undesirable or impractical in many applications, such as displays (e.g., consumer electronics, including mobile phones, tablets, computers, navigation systems, etc.), buildings (e.g., windows, shower panels, countertops, etc.), transportation vehicles (e.g., automobiles, trains, aircraft, marine vehicles, etc.), household appliances, or any application that requires an article that has excellent crack resistance while being thin and lightweight.
[0007] Although chemical strengthening is not limited in the same manner by the thickness of the glass-based article, known chemically strengthened glass-based articles fail to exhibit the stress profile of thermally tempered glass-based articles. An example of a stress profile resulting from chemical strengthening (e.g., by ion exchange) is shown in FIG. 2. In FIG. 2, a chemically strengthened glass-based article 200 comprises a first surface 201, a thickness t2, and a surface CS 210. The CS of the glass-based article 200 decreases along the first surface 201 to a DOC 230, as defined herein, where the stress transitions from a compressive stress to a tensile stress and reaches a maximum CT 220. As shown in FIG. 2, the stress profile exhibits a substantially flat CT region or a constant or nearly constant tensile stress along at least a portion of the CT region. Known chemically strengthened glass-based articles often exhibit lower maximum CT values than the maximum center value shown in FIG.
[0008] Therefore, there is a need for thin glass-based articles that exhibit improved breakage resistance. SUMMARY OF THE INVENTION
[0009] A first aspect of the present invention relates to a glass-based article comprising a first surface and a second surface opposite the first surface, both defining a thickness (t); a concentration of a metal oxide that is non-zero and varies along the thickness in a range of about 0·t to about 0.3·t; and a central tension (CT) region having a maximum CT greater than or equal to 71.5 / √(t), wherein when the glass-based article breaks, the glass-based article breaks into at least 2 fragments / inch as measured using the "Fragility Test" described by Z. Tang et al. in "Automated Apparatus for Measuring the Frangibility and Fragmentation of Strengthened Glass", Experimental Mechanics (2014) 54:903-912. 2 (fragments / square inch), where the sample size used is 5.08 cm by 5.08 cm (2 inches by 2 inches). The number of fragments is divided by the area of the sample tested (unit: square inches). As used herein, the change in metal oxide concentration refers to the metal oxide concentration gradient. In one or more embodiments, the concentration of the metal oxide is non-zero and varies along the entire thickness. In one or more embodiments, the CT region may include a metal oxide that is non-zero and varies along the thickness in the range of about 0·t to about 0.3·t. One or more embodiments of the glass-based article may include a thickness t of about 3 mm or less, 2 mm or less, or about 1 mm or less.
[0010] A second aspect of the present invention relates to a glass-based article comprising a first surface and a second surface opposite the first surface, both defining a thickness (t) of about 3 mm or less, and a stress distribution extending along the thickness, wherein all points of the stress distribution between a thickness range from about 0·t to a maximum of 0.3·t and a thickness range greater than 0.7·t to t have a tangent line whose absolute value of the slope is greater than about 0.1 MPa / μm, wherein the stress distribution comprises a maximum CS, a DOC, and a maximum CT greater than or equal to 71.5 / √(t), wherein the ratio of the absolute value of the maximum CT to the maximum CS is in the range of about 0.01-0.2, and wherein the DOC is about 0.1·t or greater.
[0011] A third aspect of the present invention relates to a glass-based article comprising a first surface and a second surface opposite the first surface, both defining a thickness (t), a concentration of a metal oxide that is non-zero and varies along the thickness in a range of about 0·t to about 0.3·t (0·t to about 0.4·t or 0·t to about 0.45·t); a surface compressive stress greater than about 200 MPa or greater; and a central tension region having a maximum CT greater than or equal to 71.5 / √(t).
[0012] A fourth aspect of the present invention is directed to a glass-based article comprising: a first surface and a second surface opposite the first surface, both defining a thickness (t); a metal oxide forming a concentration gradient, wherein the concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface, and increases from the point to the second surface, wherein the concentration of the metal oxide at the point is non-zero, and the glass-based article has a thermal conductivity greater than about 0 J / m 2 To less than 20J / m 2 of stored tensile energy and a Young's modulus of about 70 GPa or more.
[0013] A fifth aspect of the present invention relates to a glass-based article comprising: a first surface and a second surface opposite to the first surface, both defining a thickness (t) of about 3 mm or less; and a stress distribution extending along the thickness, wherein all points of the stress distribution between a thickness range from about 0·t to a maximum of 0.3·t and a thickness range greater than 0.7·t have a tangent line whose absolute value of the slope is greater than about 0.1 MPa / μm, wherein the stress distribution comprises a maximum CS, a DOC, and a maximum CT, wherein the ratio of the absolute value of the maximum CT to the maximum CS is in the range of about 0.01-0.2, wherein the DOC is about 0.1·t or greater, and the glass-based article comprises a stress greater than about 0 J / m 2 To less than 20 J / m 2 The glass-based article has a stored tensile energy of about 100 GPa and a Young's modulus of about 70 GPa or greater. In one or more embodiments, the glass-based article comprises a non-zero concentration of a metal oxide that varies continuously throughout the thickness. In some examples, the non-zero concentration of the metal oxide varies continuously along a thickness segment of less than 10 microns.
[0014] A sixth aspect of the present invention relates to a glass-based article comprising a stress distribution having a CS region and a CT region, wherein the CT region is characterized by the equation: Stress (x) = Maximum T - (((CT n ·(n+1)) / 0.5n)·|(x / t)-0.5|n) is approximately obtained, where the maximum T is the maximum tensile value, CT nLess than or equal to the maximum T and is a positive value in MPa, x is the position along the thickness (t) (in microns), and n is 1.5 to 5. In some embodiments, the maximum CT value is in the range of about 50 MPa to about 250 MPa, and the maximum CT value is located at a depth in the range of about 0.4t to about 0.6t. In one or more embodiments, the stress distribution has a slope of about 20 MPa / micron to about 200 MPa / micron in the thickness range from about 0t to about 0.1t. In one or more embodiments, the stress distribution is approximated by a plurality of error functions measured in the range of 0.5t to the surface.
[0015] According to one or more embodiments of the glass-based article of the present invention, the monovalent ion of the metal oxide generates stress along the thickness range (i.e., from about 0·t to about 0.3·t, from about 0·t to about 0.4·t, or from about 0·t to about 0.45·t). In one or more embodiments, the concentration of the metal oxide decreases from the first surface to a point between the first surface and the second surface, and the concentration increases from the point to the second surface.
[0016] In one or more embodiments, the concentration of the metal oxide throughout the thickness is about 0.05 mol% or more. For example, in one or more embodiments, the concentration of the metal oxide at the first surface may be about 1.5 times (or more) the concentration of the metal oxide at a depth equal to about 0.5·t. In an exemplary embodiment, the glass-based article includes a total concentration of metal oxides of about 1 mol% to about 15 mol%. In one or more embodiments, examples of metal oxides include one or more of Li2O, Na2O, K2O, Rb2O, and Cs2O. In one or more embodiments, the monovalent ion of the metal oxide has the largest ionic diameter among all metal oxides in the glass-based substrate or article.
[0017] In one or more embodiments, the CT region comprises a non-zero metal oxide that varies along the thickness in the range of about 0·t to about 0.3·t. In one or more embodiments of the glass-based articles herein, the maximum CT is greater than or equal to 71.5 / √(t) (MPa), where "71.5" is in MPa·(mm)^0.5 and "t" is in millimeters (mm).
[0018] Some embodiments of the glass-based article include a first metal oxide concentration and a second metal oxide concentration. In some embodiments, the first metal oxide concentration in a first thickness range of about 0·t to about 0.5·t is in a range of about 0 mol% to about 15 mol%. In some embodiments, the second metal oxide concentration in a second thickness range of about 0 microns to about 25 microns is in a range of about 0 mol% to about 10 mol%. The glass-based article may include an optional third metal oxide.
[0019] In one or more embodiments, the glass-based articles described herein may exhibit a surface compressive stress (CS) greater than the maximum CT. One or more embodiments of the glass-based articles described herein may include a surface CS of about 300 MPa or greater. In some examples, the surface CS is exhibited when the glass-based article has a thickness of about 2 mm or less. In one or more embodiments, the glass-based article exhibits a combination of a surface CS of about 200 MPa or greater and a chemical layer depth of about 0.4·t or deeper. In one or more embodiments, the glass-based article includes a CS that extends from the first surface to the DOC, and the DOC is about 0.1·t or deeper. In some examples, the ratio of the absolute value of the maximum CT to the surface CS is about 0.1-about 0.8.
[0020] In one or more embodiments, the glass-based article has an amorphous structure. In some embodiments, the glass-based article may include a crystalline structure.
[0021] In one or more embodiments, the glass-based articles described herein may have a transmittance of about 88% or greater in the wavelength range of about 380 nm to about 780 nm. In some examples, the glass-based articles described herein may have the following CIE LAB color space coordinates under CIE illuminant F02: L* value of about 88 or greater, a* value in the range of about -3 to about +3, and b* value in the range of about -6 to about +6.
[0022] In one or more embodiments, the glass-based articles herein may comprise a Young's modulus of about 70 GPa or greater. In some embodiments, the glass-based articles herein comprise a liquidus viscosity of less than about 100 kilopoise (kP). In one or more embodiments, the glass-based articles herein exhibit a Young's modulus of about 0.65 MPa·m 1 / 2or greater fracture toughness. In one or more embodiments, the glass-based article herein comprises one or more of any of the following compositions: a composition comprising a combined amount of about 15 mol% or less of Al2O3 and Na2O, a composition comprising about 4 mol% or more of Na2O, a composition comprising any one or more of B2O3, ZnO, and a composition substantially free of P2O5. In one or more embodiments, the glass-based article may have a hardness of about 450 μm at about 460°C. 2 / hour (square micrometers / hour) or greater monovalent ion (e.g., sodium ion or potassium ion) diffusivity. In some embodiments, the monovalent ion diffusivity is exhibited at a DOC greater than about 0.15·t and a surface CS of 1.5 times or greater than the maximum CT.
[0023] In one or more embodiments, the glass-based articles described herein exhibit suitable fracture characteristics. For example, in one or more embodiments, when the glass-based article is fractured by a single event (i.e., a single impact such as a drop or a single impact with a tool), the glass-based article fractures into at least 2 fragments / inch. 2 (fragments / square inch), wherein the sample size used is 5.08 cm x 5.08 cm (2 in x 2 in) square (measured using the "Fragility Test" described in Z. Tang et al., "Automated Apparatus for Measuring the Frangibility and Fragmentation of Strengthened Glass," Experimental Mechanics (2014) 54:903-912). The number of fragments is divided by the area of the sample tested (in square inches). In some embodiments, when the glass-based article breaks, the glass-based article breaks into at least 1 fragment / inch 2 Up to 40 pieces / inch 2 (chips / square inch), wherein the sample size used was 5.08 cm x 5.08 cm (2 inches x 2 inches) square.
[0024] A seventh aspect of the present invention relates to the use of a glass substrate in a strengthened glass-based article. In one or more embodiments, the glass substrate comprises (mol %): about 68-about 75 SiO2; about 12-15 Al2O3; about 0.5-about 5 B2O3; about 2-about 10 Li2O; about 0-about 6 Na2O; about 1-about 4 MgO; about 0-about 3 ZnO; and about 0-about 5 CaO, wherein the glass substrate is ion-exchangeable and amorphous. In one or more embodiments, the glass substrate exhibits one or more of the following properties: a ratio of Li2O to R2O of about 0.45–about 1; a difference between the total content of R2O and the content of Al2O3 of about -5 to about 0; R x The difference between the total content (mol %) of O and the content of Al2O3 is about 0 to about 3; and the ratio of the content (mol %) of MgO to the total content (mol %) of RO is about 0 to about 1, and the glass substrate substantially does not contain a nucleating agent.
[0025] An eighth aspect of the present invention is directed to a glass substrate comprising a composition, the composition comprising (in mole %) about 68 to about 75 SiO2; about 12 to about 15 Al2O3; about 0.5 to about 5 B2O3; about 2 to about 10 Li2O; about 0 to about 6 Na2O; about 1 to about 4 MgO; about 0 to about 3 ZnO; and about 0 to about 5 CaO, wherein the glass substrate is ion-exchangeable and amorphous. In one or more embodiments, the glass substrate exhibits one or more of the following properties: a ratio of Li2O to R2O of about 0.45 to about 1; a difference between the total content of R2O and the content of Al2O3 of about -5 to about 0; R x The difference between the total content (mol %) of O and the content of Al2O3 is about 0 to about 3; and the ratio of the content (mol %) of MgO to the total content (mol %) of RO is about 0 to about 1. In one or more embodiments, the glass substrate is substantially free of nucleating agents.
[0026] A ninth aspect of the present invention relates to a glass substrate comprising (in mole %) about 68 to about 75 SiO2; about 12 to 15 Al2O3; about 0.5 to about 5 B2O3; about 2 to about 10 Li2O; about 0 to about 6 Na2O; about 1 to about 4 MgO; about 0 to about 3 ZnO; and about 0 to about 5 CaO, wherein the glass substrate is amorphous and strengthened. In one or more embodiments, the Na2O concentration varies in the glass substrate. In one or more embodiments, the glass substrate is substantially free of nucleating agents. In one or more embodiments, the strengthened glass substrate exhibits any one or more of the following compositional relationships: a ratio of Li2O to R2O of about 0.45–about 1; a difference between the total content of R2O and the content of Al2O3 of about -5 to about 0; R xThe difference between the total content (mol %) of O and the content of Al2O3 is about 0 to about 3; and the ratio of the content (mol %) of MgO to the total content (mol %) of RO is about 0 to about 1.
[0027] The tenth aspect of the present invention relates to a device comprising: a shell having a front side, a back side and a side side; an electrical component at least partially located within the shell; a display located at or adjacent to the front side of the shell; and a covering substrate disposed on the display, wherein the covering substrate comprises a glass-based product as described in an embodiment of the present invention.
[0028] Other features and advantages of the present invention are set forth in the following detailed description, some of which will be readily apparent to those skilled in the art from the description or recognized by practicing the various embodiments described herein, including the following detailed description, claims, and accompanying drawings.
[0029] It should be understood that the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overall review or framework for understanding the nature and characteristics of the claims. The accompanying drawings provide a further understanding of the present invention, and the drawings are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiments of the present invention and, together with the description, are used to explain the principles and operations of the various embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] FIG1 is a cross-sectional view of a known heat-tempered glass product in the thickness direction;
[0031] FIG2 is a cross-sectional view of a known chemically strengthened glass product in the thickness direction;
[0032] Figure 3 is a cross-sectional view through the thickness of a chemically strengthened glass-based article according to one or more embodiments of the present invention;
[0033] Figure 4 are various stress distribution diagrams of one or more embodiments of the present invention;
[0034] Figure 5 is a schematic cross-sectional view of a ring-on-ring device;
[0035] Figure 6 is a schematic cross-sectional view of a test apparatus for conducting an inverted ball on sandpaper (IBoS) test as described herein;
[0036] Figure 7 is a schematic diagram of the main failure mechanisms that typically occur in glass-based products for portable or handheld electronic devices, the failures being caused by damage introduction and bending;
[0037] Figure 8is a flow chart of the method for performing IBoS testing in the device described in this article;
[0038] Fig. 9 is a graph of Na2O concentrations of known chemically strengthened glass-based articles and glass-based articles according to one or more embodiments of the present invention;
[0039] Fig.10 is a graph of CT value and DOC value as a function of ion exchange time for one or more embodiments of the present invention;
[0040] Fig.11 is a graph comparing stress distribution as a function of depth in known chemically strengthened glass-based articles and glass-based articles according to one or more embodiments of the present invention;
[0041] Fig.12 Shows stress distribution diagrams for known chemically strengthened glasses and glass-ceramics;
[0042] Fig.13 Stress distribution diagrams showing glasses and glass ceramics according to one or more embodiments of the present invention;
[0043] Fig.13A A graph showing the failed height in the drop test of Example 3D;
[0044] Fig.14 is a comparison graph between known stress profiles of chemically strengthened glass-based articles and glass-based articles of one or more embodiments of the present invention;
[0045] Fig.15 shows the stress distribution as a function of thickness for Examples 4A-4D;
[0046] Fig.16 Discrete stored tensile energy data points are shown for Examples 4B-4D;
[0047] Fig.17 shows the concentration of K2O and Na2O as a function of depth for Examples 4A-4D;
[0048] Fig.18 show Fig.17 Same data as above, but using a different scale to more clearly show the concentration of Na2O as a function of depth;
[0049] Fig.19 shows the stress distribution as a function of depth for Examples 4A and 4C-4F;
[0050] Fig. 20 show Fig.19 Figures of different scales;
[0051] Fig.21shows stress distribution as a function of depth for Examples 5A-5G;
[0052] Fig. 22 shows the DOC values of Examples 5A-5G as a function of the duration of the second and / or third ion exchange step;
[0053] Fig.23 shows the CT values of Examples 5A-5G as a function of the duration of the second and / or third ion exchange step;
[0054] Fig.24 Shows CT as a function of ion exchange time for Examples 6A-6G;
[0055] Fig.25 Shows the change in central tension values and stored tensile energy of Examples 6A-6G as a function of ion exchange time;
[0056] Fig.26 shows the stress distribution as a function of depth for Comparative Example 7A and Example 7B;
[0057] Fig. 27 shows the storage tensile energy as a function of maximum CT for Comparative Example 7A and Example 7B;
[0058] Fig.28 shows the storage tensile energy as a function of CT for Comparative Example 7C and Example 7D;
[0059] Fig.29 The unqualified drop heights of Examples 2 and 8 and Comparative Examples 8A and 8B are shown;
[0060] Fig.30 The ring-to-ring grinding results of Examples 2 and 8 and Comparative Examples 8A and 8B are shown;
[0061] Fig.31 The Weibull plots show the 4-point bending results of Examples 2 and 8B;
[0062] Fig.32 The maximum CT values of Examples 9A to 9E are shown as a function of ion exchange time;
[0063] Fig.33 shows the measured stress for Example 9D as a function of depth extending from the surface of the glass-based article into the glass-based article;
[0064] Fig.34 The unqualified load values after grinding the glass-based product of Example 10A under different loads or pressures are shown;
[0065] Fig.35The glass-based article of Example 10A is shown to fail at a height after being dropped onto 180-grit sandpaper and then onto 30-grit sandpaper;
[0066] Fig.36 The glass-based articles of Example 10A and Comparative Example 10B are shown to fail at a height after being dropped onto No. 30 sandpaper;
[0067] Fig.37 is a graph comparing the average failure loads of the glass-based articles of Example 10A and Comparative Example 10B after being ground with a load or pressure of 25 psi;
[0068] Fig.38 is a graph comparing the average failure loads of the glass-based articles of Example 10A and Comparative Example 10B after being ground with a load or pressure of 45 psi;
[0069] Fig.39 is a front view of an electronic device incorporating a glass-based article as described in one or more embodiments herein; and
[0070] Fig.40 The following are the IBoS test results of some example samples. DETAILED DESCRIPTION OF THE INVENTION
[0071] Various embodiments will be described in detail below, examples of which are shown in the embodiments and drawings.
[0072] In the following description, in several views shown in all drawings, the same reference numerals represent similar or corresponding parts. It should also be understood that, unless otherwise stated, terms such as "top", "bottom", "outward", "inward", etc. are terms for convenience and should not be regarded as restrictive terms. In addition, whenever a group is described as comprising at least one of a group of elements and their combinations, it should be understood that the group can contain any number of these listed elements in the form of a single element or a combination of them, or mainly consist of any number of these listed elements, or consist of any number of these listed elements. Similarly, whenever a group is described as consisting of at least one element in a group of elements or their combinations, it should be understood that the group can consist of any number of these listed elements in the form of a single element or a combination of them. Unless otherwise stated, the numerical range listed includes both the upper and lower limits of the range, and any range between the upper and lower limits. Unless otherwise stated, the modifiers "a" or "an" and their corresponding modifiers "the" used herein mean "at least one", or "one or more." It should also be understood that the various features disclosed in the specification and drawings can be used in any and all combinations.
[0073] As used herein, the terms "glass-based article" and "glass-based substrate" are used in their broadest sense to include any object made in whole or in part of glass. Glass-based articles include laminates of glass and non-glass materials, laminates of glass and crystalline materials, and glass-ceramics (including amorphous and crystalline phases). Unless otherwise indicated, all compositions are expressed in mole percent (mol %).
[0074] It should be noted that the terms "substantially" and "approximately" may be used herein to represent the inherent degree of uncertainty that can be caused by any quantitative comparison, value, measurement or other method of representation. These terms are also used herein to represent that the representation of a quantity can vary from a stated reference value to a certain extent without resulting in a change in the basic function of the object for which it is intended.
[0075] As used herein, the term "approximately" refers to quantities, dimensions, formulas, parameters and other quantities and features that are not precise or need not be precise, but may be roughly and / or larger or smaller as required, such as reflection tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those skilled in the art. When the term "about" is used to describe the value or endpoint of a range, it should be understood that the present invention includes the specific value or endpoint referenced. Regardless of whether the numerical value or endpoint of a range in the present invention uses "about", the numerical value or endpoint of the range includes two embodiments: one is modified with "about" and the other is not modified with "about". It should also be understood that the endpoint values of each range are meaningful in combination with another endpoint value and independently of another endpoint value.
[0076] Unless otherwise indicated, all temperatures are expressed in degrees Celsius (°C). As used herein, the term "softening point" refers to the point at which the viscosity of a glass is approximately 10 7.6 The term "annealing point" refers to the temperature at which the viscosity of the glass is about 10 13.2 The term "200 poise temperature (T 200P )" refers to the temperature at which the viscosity of glass is about 200 poise. The term "10 11 The "Poise temperature" refers to the viscosity of the glass is about 10 11 The term "35kP temperature (T 35kP )” refers to the temperature at which the viscosity of the glass is about 35 kilopoise (kP), and the term “160 kP temperature (T 160kP )" refers to the temperature at which the viscosity of the glass is approximately 160 kP.
[0077] With reference to all the drawings, and particularly to FIGS. 1-3, it should be understood that the purpose of these drawings is to describe specific embodiments of the present invention, and these drawings do not constitute limitations on the specification of the present invention or the appended claims. For the sake of clarity and conciseness, the drawings are not necessarily drawn to scale, and certain features and certain views of the drawings may be shown in a scaled-up or schematic manner.
[0078] As used herein, DOC refers to the depth at which stress in a glass-based article changes from compressive to tensile. At the DOC, stress changes from positive stress (compressive stress) to negative stress (tensile stress) (eg, 130 in FIG. 1 ), thus exhibiting a stress value of zero.
[0079] As used herein, the terms "chemical depth", "layer chemical depth" and "chemical layer depth" are used interchangeably to refer to the depth to which ions of metal oxides or alkali metal oxides (e.g., metal ions or alkali metal ions) diffuse into a glass-based article and the depth at which the ion concentration reaches a minimum (as measured by electron probe microanalysis (EPMA) or glow discharge-optical emission spectroscopy (GD-OES)). Specifically, to assess the depth of diffusion of Na2O or Na+ ions, EPMA and a surface stress meter (described in detail below) can be used to measure the ion concentration.
[0080] Unless otherwise specified, according to common practice in the art, compression is expressed as negative stress (<0) and tension is expressed as positive stress (>0). However, in this specification, when compressive stress CS is mentioned, positive or negative values are not mentioned, that is, as described herein, CS=|CS|.
[0081] Described herein are thin, chemically strengthened glass-based articles comprising glass, such as silicate glass, including alkali-containing glass, and glass-ceramics, which can be used as cover glass for mobile electronic devices or touch-sensitive displays. The glass-based articles can also be used in displays (or display articles) (e.g., billboards, sales systems, computers, navigation systems, etc.), architectural articles (walls, fixtures, panels, windows, etc.), transportation articles (e.g., in automotive applications, trains, aircraft, marine craft, etc.), or electrical articles (e.g., washing machines, dryers, dishwashers, refrigerators, etc.), or any article requiring some resistance to cracking.
[0082] Specifically, the glass-based articles described herein are thin and exhibit stress distributions that are typically only available after tempering of thick glass articles (e.g., having a thickness of about 2 mm or 3 mm or more). The glass-based articles exhibit a unique stress distribution along their thickness. In some cases, the glass-based articles described herein exhibit a higher surface CS than tempered glass articles. In one or more embodiments, the glass-based articles have a compressive stress layer extending deeper into the glass-based article (the decrease or increase in CS is slower than that of known chemically strengthened glass-based articles), and the glass-based articles exhibit significantly improved fracture resistance, even if the glass-based article or a device containing it falls on a hard surface (e.g., granite) or a hard and rough surface (e.g., asphalt). The glass-based articles of one or more embodiments exhibit a higher maximum CT value than some known chemically strengthened glass substrates.
[0083] CS and potassium ion penetration depth (referred to as "potassium DOL") are measured using methods known in the art. Potassium DOL is different from DOC because it represents the potassium penetration depth in the ion exchange process. For the products herein, potassium DOL is generally less than DOC. CS and potassium DOL are measured by a surface stress meter (FSM) using commercially available equipment (e.g., FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan)). Surface stress measurements rely on accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. SOC is measured according to an improved version of ASTM standard C770-98 (2013), Scheme C (entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient"), which is incorporated herein by reference in its entirety. Improvements in this version include using a glass disk as the specimen, 5-10 mm thick and 12.7 mm in diameter, which is isotropic and uniform, core-drilled, polished and parallel on both sides. The improvements also include calculating the maximum force F to be applied. 最大 The force should be sufficient to produce a compressive stress of 20 MPa or more. 最大 The calculation is as follows:
[0084] F 最大 =7.854*D*h
[0085] in:
[0086] F 最大 = force, in Newtons
[0087] D = disc diameter
[0088] h = thickness of the optical path
[0089] For each application of force, the stress is calculated as follows:
[0090] σ MPa =8F / (π*D*h)
[0091] in:
[0092] F = force, in Newtons
[0093] D = disc diameter
[0094] h = thickness of the optical path
[0095] The DOC and maximum CT values are measured using a scattered light polariscope (SCALP) technique known in the art. The refracted near field (RNF) method or SCALP can be used to measure the stress distribution. When the RNF method is used, the maximum CT value provided by the SCALP is used. Specifically, the stress distribution measured by the RNF is force balanced and calibrated to the maximum CT value provided by the SCALP measurement. The RNF method is described in U.S. Patent No. 8,854,623, entitled "System and Method for Optical Characterization of Glass", which is incorporated herein by reference in its entirety. Specifically, the RNF method includes placing a glass-based article near a reference block, generating a polarization-switched beam that switches between orthogonal polarizations at 1 Hz and 50 Hz, measuring the power in the polarization-switched beam, and generating a polarization-switched reference signal, wherein the measured powers of each orthogonal polarization light are within 50% of each other. The method also includes transmitting the polarization-switched beam through reference blocks and glass samples at different depths to enter the glass sample, and then relaying the transmitted polarization-switched beam to a signal detector using an optical relay system, which generates a polarization-switched detection signal. The method also includes dividing the detection signal by a reference signal to form a standardized detection signal and obtaining the distribution characteristics of the glass sample from the standard detection signal. The RNF distribution is then flattened and applied to the CT region. As described above, the FSM technique is used for the slope of the stress distribution in the surface CS and the CS region adjacent to the surface.
[0096] As described above, the glass-based articles described herein are chemically strengthened by ion exchange and exhibit a stress profile that is different from known strengthened glass articles. As used herein, a glass-based substrate is generally unstrengthened and a glass-based article generally refers to a glass-based substrate that has been strengthened (e.g., by ion exchange). In this process, ions at or near the surface of the glass-based article are replaced or exchanged with larger ions of the same valence or oxidation state. In those embodiments where the glass-based article comprises an alkali aluminosilicate glass, the ions in the surface layer of the glass and the larger ions are monovalent alkali metal cations, such as Li +(when present in glass-based products), Na + , K + , Rb + and Cs + Alternatively, the monovalent cations in the surface layer may be monovalent cations other than alkali metal cations, such as Ag. + In this embodiment, the monovalent ions (or cations) exchanged into the glass-based substrate create stress in the resulting glass-based article.
[0097] The ion exchange process is generally performed by immersing the glass-based substrate in a molten salt bath (or two or more molten salt baths) containing larger ions to be exchanged with smaller ions in the glass substrate. It should be noted that aqueous salt baths may also be used. In addition, the composition of the salt bath may contain more than one type of larger ions (e.g., Na+ and K+) or a single larger ion. It will be appreciated by those skilled in the art that the parameters of the ion exchange process (including but not limited to bath composition and temperature, immersion time, the number of immersions of the glass-based article in the salt bath (or multiple salt baths), the use of multiple salt baths, other steps (e.g., annealing and washing, etc.)) are generally determined by the composition of the glass-based article (including the article structure and any crystalline phases present), and the desired DOC and compressive stress of the glass-based article obtained by the strengthening operation. For example, ion exchange of the glass-based substrate can be achieved by immersing the glass-based substrate in at least one molten salt bath containing salts, such as but not limited to nitrates, sulfates, and chlorides including larger alkali metal ions. Common nitrates include KNO3, NaNO3, LiNO3, NaSO4 and combinations thereof. The temperature of the molten salt bath is generally about 380°C to about 450°C, and the immersion time is about 15 minutes to 100 hours, depending on the glass thickness, bath temperature and glass (or monovalent ion) diffusion. However, temperatures and immersion times different from those described above may also be used.
[0098] In one or more embodiments, the glass-based substrate may be immersed in a 100% NaNO3 molten salt bath having a temperature of about 370°C to about 480°C. In one or more embodiments, the glass-based substrate may be immersed in a molten salt bath containing about 5% to about 90% KNO3 and about 10% to about 95% NaNO3. In some embodiments, the glass-based substrate may be immersed in a mixed molten salt bath containing Na2SO4 and NaNO3 and having a wide temperature range (e.g., up to about 500°C). In one or more embodiments, the glass-based article may be immersed in a second bath after the first bath immersion. The second bath immersion may include immersion in a molten salt bath containing 100% KNO3 for 15 minutes to 8 hours.
[0099] In one or more embodiments, the glass-based substrate may be immersed in a mixed molten salt bath comprising NaNO3 and KNO3 (e.g., 49% / 51%, 50% / 50%, 51% / 49%) at a temperature below about 420°C (e.g., about 400°C or about 380°C) for less than about 5 hours, or even about 4 hours or less.
[0100] The ion exchange conditions can be adjusted to provide a "peak" or increase the slope of the stress profile at or near the surface of the resulting glass-based article. Due to the unique properties of the glass compositions used in the glass-based articles used herein, the peak can be achieved in a single bath or multiple baths, the baths having a single composition or a mixed composition.
[0101] like Figure 3 As shown, one or more embodiments of the glass-based article 300 include a first surface 302 and a second surface 304 opposite the first surface, both of which define a thickness t. In one or more embodiments, the thickness t can be less than or equal to about 3 mm (e.g., about 0.01 mm to about 3 mm, about 0.1 mm to about 3 mm, about 0.2 mm to about 3 mm, about 0.3 mm to about 3 mm, about 0.4 mm to about 3 mm, about 0.01 mm to about 2.5 mm, about 0.01 mm to about 2 mm, about 0.01 mm to about 1.5 mm, about 0.01 mm to about 1 mm, about 0.01 mm to about 0.9 mm, about 0.01 mm to about 0.8 mm, about 0.01 mm to about 0.7 mm, about 0.01 mm to about 0.6 mm, about 0.01 mm to about 0.5 mm, about 0.1 mm to about 0.5 mm, or about 0.3 mm to about 0.5 mm).
[0102] The glass-based article includes a stress distribution extending from the first surface 302 to the second surface 304 (or along the entire length of the thickness t). Figure 3 In the illustrated embodiment, stress profile 312 is shown with the y-axis representing stress magnitude and the x-axis representing thickness or depth within the glass-based article.
[0103] like Figure 3 As shown, the stress profile 312 includes a CS layer 315 (having a surface CS 310), a CT layer 325 (maximum CT 320), and a DOC 330 where the stress profile 312 changes from compression to tension. The associated depth or length 317 of the CS layer extends from the surfaces 302, 304 to the DOC 330. The CT layer 325 also has an associated depth or length 327 (CT region or layer).
[0104] The surface CS 310 may be about 150 MPa or more or about 200 MPa or more (e.g., about 250 MPa or more, about 300 MPa or more, about 400 MPa or more, about 450 MPa or more, or about 500 MPa or more, or about 550 MPa or more). The surface CS 310 may be at most about 900 MPa, at most about 1000 MPa, at most about 1100 MPa, or at most about 1200 MPa. The surface CS values herein may also include a maximum CS. In some embodiments, the surface CS is less than the maximum CS.
[0105] The maximum CT320 may be greater than or equal to about 71.5 / √(t). In some embodiments, the maximum CT320 is about 80 MPa or more, about 85 MPa or more, or about 90 MPa or more. In some embodiments, the maximum CT320 is greater than about 80 MPa to about 100 MPa (e.g., about 85 MPa to about 100 MPa, about 90 MPa to about 100 MPa, about 80 MPa to about 95 MPa, about 80 MPa to about 90 MPa, about 85 MPa to about 95 MPa, about 88 MPa to about 92 MPa). The maximum CT320 may be located at about 0.3·t to about 0.7·t, about 0.4·t to about 0.6·t, about 0.45·t to about 0.55·t. It should be noted that one or more surface CS310 and the maximum CT320 may depend on the thickness of the glass-based article. For example, a glass-based article having a thickness of about 0.8 mm may have a maximum CT of about 85 MPa to about 100 MPa. As the thickness of the glass-based article decreases, the maximum CT may increase. In other words, the maximum CT increases as the thickness decreases (or as the glass-based article becomes thinner).
[0106] In some embodiments, the ratio of the maximum CT 320 to the surface CS 310 is from about 0.1 to about 0.8 (e.g., from about 0.1 to about 0.7, from about 0.1 to about 0.6, from about 0.1 to about 0.5, from about 0.1 to about 0.4, from about 0.1 to about 0.3, from about 0.1 to about 0.25, from about 0.1 to about 0.2, from about 0.15 to about 0.8, from about 0.2 to about 0.8, from about 0.3 to about 0.8, from about 0.4 to about 0.8, from about 0.5 to about 0.8, or from about 0.6 to about 0.8). In known chemically strengthened glass-based articles, the ratio of the maximum CT 320 to the surface CS 310 is 0.1 or less. In some embodiments, the surface CS may be 4 times (e.g., 5 times, 6 times, or 6.5 times) or more of the maximum CT. In some embodiments, the surface CS may be up to about 47.5 times the maximum CT. The surface CS may be from about 4 times up to about 7.5 times the maximum CT.
[0107] In one or more embodiments, the stress profile 312 includes a maximum CS, which is generally a surface CS 310 and can be found at one or both of the first surface 302 and the second surface 304. In one or more embodiments, the CS layer or region 315 extends along a portion of the thickness 317 to the DOC 330 and the maximum CT 320. In one or more embodiments, the DOC 330 can be about 0.1·t or higher. For example, the DOC 330 can be about 0.12·t or higher, about 0.14·t or higher, about 0.15·t or higher, about 0.16·t or higher, about 0.17·t or higher, about 0.18·t or higher, about 0.19·t or higher, about 0.20·t or higher, about 0.21·t or higher, about 0.25·t or higher. In some embodiments, the DOC 330 is less than the chemical depth. The chemical depth may be about 0.4·t or more, 0.5·t or more, about 55·t or more, or about 0.6·t or more.
[0108] In one or more embodiments, the glass-based article comprises a potassium DOL in a range of about 6 microns to about 20 microns. In some embodiments, the potassium DOL may be expressed as a function of the thickness t of the glass-based article. In one or more embodiments, the potassium DOL may be in a range of about 0.005t to about 0.05t. In some embodiments, the potassium DOL may be in a range of about 0.005t to about 0.05t, about 0.005t to about 0.045t, ... To about 0.04t, about 0.005t to about 0.035t, about 0.005t to about 0.03t, about 0.005t to about 0.025t, about 0.005t to about 0.02t, about 0.005t to about 0.015t, about 0.005t to about 0.01t, about 0.006t to about 0.05t, about 0.008t to about 0.05t, about 0.01t to about 0.05t, about 0.015t to about 0.05t, about 0.02t to about 0.05t, about 0.025t to about 0.05t, about 0.03t to about 0.05t, or about 0.01t to about 0.02t.
[0109] In one or more embodiments, the compressive stress value at the potassium DOL depth may be from about 50 MPa to about 300 MPa. In some embodiments, the compressive stress value at the potassium DOL depth may be from about 50 MPa to about 280 MPa, from about 50 MPa to about 260 MPa, from about 50 MPa to about 250 MPa, from about 50 MPa to about 240 MPa, from about 50 MPa to about 220 MPa, from about 50 MPa to about 200 MPa, from about 60 MPa to about 300 MPa, from about 70 MPa to about 300 MPa, from about 75 MPa to about 300 MPa, from about 80 MPa to about 300 MPa, from about 90 MPa to about 300 MPa, from about 100 MPa to about 300 MPa, from about 110 MPa to about 300 MPa, from about 120 MPa to about 300 MPa, from about 130 MPa to about 300 MPa, or from about 150 MPa to about 300 MPa.
[0110] In one or more embodiments, the stress profile 312 may be described as a parabola-like shape. In some embodiments, the stress profile exhibits a parabola-like shape along a region or depth of the glass-based article that exhibits tensile stress. In one or more specific embodiments, the stress profile 312 does not contain a flat stress stress curve (compressive or tensile stress) portion or a portion that exhibits a substantially constant stress (compressive or tensile stress). In some embodiments, the CT region exhibits a stress profile that is substantially free of a flat stress curve or substantially free of a constant stress. In one or more embodiments, all points of the stress profile 312 between a thickness range of about 0t up to about 0.2·t and greater than 0.8·t (or from 0·t to about 0.3·t and greater than about 0.7·t to t) contain a tangent line whose absolute value of slope is greater than about 0.1 MPa / micrometer. In some embodiments, the slope of the tangent line may have an absolute value greater than about 0.2 MPa / micrometer. In some more specific embodiments, the slope of the tangent line may have an absolute value greater than about 0.3 MPa / micrometer. In more specific embodiments, the slope of the tangent may have an absolute value greater than about 0.5 MPa / micrometer. In other words, in one or more embodiments of the stress distribution along these thickness ranges (i.e., 0t up to about 0.2·t and greater than 0.8·t, or from 0·t to about 0.3·t and about 0.7·t or higher), the stress distribution excludes tangents with a slope of 0 or a slope close to 0 or a horizontal slope. Without being limited by theory, known error functions or quasi-linear stress distributions have points along these thickness ranges (i.e., 0t up to about 0.2·t and greater than 0.8·t, or from 0·t to about 0.3·t and about 0.7·t or higher) that have tangents with a slope of 0 or a slope close to 0, i.e., they may have an absolute value of less than about 0.1 MPa / micrometer (indicating a horizontal or 0 slope stress distribution along this thickness range, as shown in Figure 2, 220). The glass-based articles of one or more embodiments of the present invention do not exhibit such a stress distribution, i.e., have a horizontal or 0 slope stress distribution along these thickness ranges, such as Figure 3 shown.
[0111] In one or more embodiments, the glass-based article exhibits a stress profile in the thickness ranges of about 0.1·t to 0.3·t and about 0.7·t to 0.9·t, the stress profile comprising a tangent line having a maximum slope and a minimum slope. In some examples, the difference between the maximum slope and the minimum slope is about 3.5 MPa / micrometer or less, about 3 MPa / micrometer or less, about 2.5 MPa / micrometer or less, or about 2 MPa / micrometer or less.
[0112] In one or more embodiments, the glass-based article includes a stress profile 312 that is substantially free of any horizontal segments extending in the depth direction or along at least a portion of the thickness t of the glass-based article. In other words, the stress profile 312 increases or decreases substantially continuously along the thickness t. In some embodiments, the stress profile is substantially free of any horizontal segments over a length of about 10 microns or more, about 50 microns or more, about 100 microns or more, about 200 microns or more in the depth direction. As used herein, the term "horizontal" means that the magnitude of the slope along the horizontal segment is less than about 0.5 MPa / micron or less than about 0.2 MPa / micron. In some embodiments, one or more portions of the stress profile are substantially free of any horizontal segments at a depth of about 5 microns or more (e.g., 10 microns or more or 15 microns or more) from the first surface and / or the second surface. For example, along a depth of about 0 microns to less than about 5 microns from the first surface, the stress profile may include a linear segment, but at a depth of about 5 microns or more from the first surface, the stress profile may be substantially free of horizontal segments. As used herein, the term "linear" includes linear segments having a horizontal slope as well as linear segments without a horizontal slope, examples of the latter being Fig.33 , at a depth of about 12 microns from the surface.
[0113] In some embodiments, the stress profile may include a linear segment at a depth of about 0t up to about 0.1t, and may be substantially free of a horizontal segment at a depth of about 0.1t to about 0.4t. In some embodiments, the magnitude (absolute value) of the slope of the stress profile at a thickness range of about 0t to about 0.1t is about 20 MPa / micron to about 200 MPa / micron. As described herein, this embodiment can be formed using a single ion exchange method, in which the salt bath includes two or more alkali metal salts or a mixed alkali metal salt bath, or using a multi (e.g., 2 or more) ion exchange method.
[0114] In one or more embodiments, the glass-based article may be used along the CT region ( Figure 3 327 in ). For example, in some embodiments, the stress distribution along the CT region (where the stress is tensile stress) can be approximated by the equation. In some embodiments, the stress distribution along the CT region can be approximated by equation (1):
[0115] Stress (x) = Maximum T – (((CT n (n+1)) / 0.5 n )·|(x / t)-0.5| n ) (1)
[0116] In equation (1), Stress(x) is the stress value at location x. Here stress is positive (tensile). In equation (1), Max T is the maximum tensile value, CT n is the stretch value at n and is less than or equal to the maximum T. Maximum T and CT n are all positive values in MPa. The value x is the position along the thickness (t) in micrometers, ranging from 0 to t; x = 0 is the surface ( Figure 3 302), x = 0.5t is the center of the glass-based product (where stress (x) = maximum T), x = t is the reverse side ( Figure 3 304). The maximum T used in equation (1) is equal to the maximum CT, which may be greater than or equal to about 71.5 / √(t). In some embodiments, the maximum T used in equation (1) may be greater than about 80 MPa to about 100 MPa (e.g., about 85 MPa to about 100 MPa, about 90 MPa to about 100 MPa, greater than about 80 MPa to about 95 MPa, greater than about 80 MPa to about 90 MPa, or about 85 MPa to about 95 MPa), and n is a fitting parameter of 1.5 to 5 (e.g., about 2-4, 2-3, or 1.8-2.2) or about 1.5 to about 2. In one or more embodiments, n=2 may provide a parabolic stress distribution, and an exponent derived from n=2 provides a stress distribution close to a parabolic distribution. Figure 4 Various stress distributions based on changes in the fitting parameter n are shown for one or more embodiments of the present invention.
[0117] In one or more embodiments, when there is a compressive stress peak on one or both major surfaces of the glass-based article, CTn may be less than the maximum T. In one or more embodiments, when there is no compressive stress peak on one or both major surfaces of the glass-based article, CTn is equal to the maximum T.
[0118] In some embodiments, the stress profile can be modified by heat treatment. In this embodiment, the heat treatment can be performed before any ion exchange process, between exchange processes, or after all ion exchange processes. In some embodiments, the heat treatment can reduce the absolute value of the magnitude of the slope of the stress profile at or near the surface. In some embodiments, when a steep or large slope is required for the surface, an ion exchange process after heat treatment can be used to provide a "peak" or to increase the slope of the stress profile at or near the surface.
[0119] In one or more embodiments, a stress distribution 312 is generated due to a change in the non-zero concentration of the metal oxide along a portion of the thickness. As described above, the change in the concentration of the metal oxide may refer to a metal oxide concentration gradient. In some embodiments, the concentration of the metal oxide is non-zero and varies along two thickness ranges of about 0·t to about 0.3·t. In some embodiments, the concentration of the metal oxide is non-zero and varies along a thickness range of about 0·t to about 0.35·t, about 0·t to about 0.4·t, about 0·t to about 0.45·t, or about 0·t to about 0.48·t. The metal oxide may be described as generating stress in a glass-based article. The concentration change along the above-referenced thickness range may be continuous. The concentration change may include a change in the metal oxide concentration of about 0.2 mol% along a thickness segment of about 100 microns. The change may be measured by methods known in the art (including microprobes), as described in Example 1. A metal oxide having a non-zero concentration and varying along a portion of the thickness may be described as generating stress in a glass-based article.
[0120] The concentration variation along the reference thickness range may be continuous. In some embodiments, the concentration variation along a thickness section of about 10 microns to about 30 microns may be continuous. In some embodiments, the concentration of the metal oxide decreases to a value from the first surface to a point between the first surface and the second surface, and the concentration of the metal oxide increases from the point to the second surface.
[0121] The concentration of metal oxides may include more than one metal oxide (e.g., a combination of Na2O and KO). In some embodiments, when two metal oxides are used and the ionic radii are different from each other, the concentration of larger radius ions is greater than the concentration of smaller radius ions at a shallower depth, while the concentration of smaller radius ions is greater than the concentration of larger radius ions at a deeper depth. For example, when a single salt bath containing Na and K is used in an ion exchange process, the glass-based article has a greater concentration of K+ ions than Na+ ions at a shallower depth, and a greater concentration of Na+ ions than K+ ions at a deeper depth. This is in part due to the size of the univalent ions that enter the glass to exchange for smaller univalent ions. In the glass-based article, the area at or near the surface has a higher CS due to the high content of larger ions (i.e., K+ ions) at or near the surface. The higher CS can be manifested by a stress distribution having a steep slope at or near the surface (i.e., a peak in the stress distribution at the surface).
[0122] As previously described, a concentration gradient or variation of one or more metal oxides is produced by chemically strengthening a glass-based substrate, wherein a plurality of first metal ions in the glass-based substrate are exchanged with a plurality of second metal ions. The first ions may be ions of lithium, sodium, potassium, and rubidium. The second metal ions may be ions of one of sodium, potassium, rubidium, and cesium, provided that the ionic radius of the second alkali metal ion is greater than the ionic radius of the first alkali metal ion. The second metal ion is present in the glass-based substrate in the form of its oxide (e.g., Na2O, KO, Rb2O, Cs2O, or a combination thereof).
[0123] In one or more embodiments, the metal oxide concentration gradient extends along most of the thickness t or the entire thickness t of the glass-based article, including the CT layer 327. In one or more embodiments, the concentration of the metal oxide in the CT layer 327 is about 0.5 mol% or greater. In some embodiments, the concentration of the metal oxide along the entire thickness of the glass-based article can be about 0.5 mol% or greater (e.g., about 1 mol% or greater), and is maximum at the first surface 302 and / or the second surface 304, and continuously decreases significantly to a value at a point between the first surface 302 and the second surface 304. The concentration of the metal oxide at this point is the lowest along the entire thickness t; however, the concentration is still non-zero at this point. In other words, the non-zero concentration of the specific metal oxide extends along most of the thickness t (as described herein) or the entire thickness t. In some embodiments, the lowest concentration of the specific metal oxide is in the CT layer 327. The total concentration of the specific metal oxide in the glass-based article can range from about 1 mol% to about 20 mol%.
[0124] In one or more embodiments, the glass-based article has a first metal oxide concentration and a second metal oxide concentration, the first metal oxide concentration ranging from about 0 mol% to about 15 mol% along a first thickness ranging from about 0t to about 0.5t, and the second metal oxide concentration ranging from about 0 mol% to about 10 mol% along a second thickness ranging from about 0 microns to about 25 microns (or about 0 microns to about 12 microns); however, along most of the thickness or the entire thickness of the glass-based article, the concentration of the first metal oxide and / or the second metal oxide is non-zero. The glass-based article may have an optional third metal oxide concentration. The first metal oxide may include Na2O, and the second metal oxide may include K2O.
[0125] The concentration of the metal oxide can be determined from a baseline amount of the metal oxide in the glass-based article before the article is modified to include a concentration gradient of the metal oxide.
[0126] In one or more embodiments, the glass-based articles may be described in terms of the manner in which they break, and the fragments resulting from such breakage, which may be tested by a "Frangibility Test", such as Z. Tang et al., Automated Apparatus for Measuring the Frangibility and Fragmentation of Strengthened Glass. Experimental Mechanics (2014) 54: 903-912. In one or more embodiments, upon breaking, the glass-based article breaks into two or more fragments per square inch (or 6.4516 square centimeters) of the glass-based article (before breaking). In some cases, the glass-based article breaks into 3 or more, 4 or more, 5 or more, or 10 or more fragments per square inch (or 6.4516 square centimeters) of the glass-based article (before breaking). In some cases, upon fracture, the glass-based article breaks into fragments such that 50% or more of the fragments have a surface area less than 5%, less than 2%, or less than 1% of the surface area of the glass-based article (before fracture) (the sample size used was a 5.08 cm x 5.08 cm (2 inch x 2 inch) square). In some embodiments, upon fracture, the glass-based article breaks into fragments such that 90% or more, or even 100% of the fragments have a surface area less than 5%, less than 2%, or less than 1% of the surface area of the glass-based article (before fracture).
[0127] In one or more embodiments, after chemically strengthening the glass-based article, the resulting stress profile 312 of the glass-based article provides improved fracture resistance. For example, in some embodiments, after fracture, the glass-based article comprises fragments having an average longest cross-sectional dimension less than or equal to about 2·t (e.g., 1.8·t, 1.6·t, 1.5·t, 1.4·t, 1.2·t, or 1.·t or less) (as determined by a "fragility test", such as according to Z. Tang et al. Automated Apparatus for Measuring the Frangibility and Fragmentation of Strengthened Glass. Experimental Mechanics (2014) 54:903-912). The number of fragments is divided by the area of the sample tested (in square inches), and the sample size used is 5.08 cm×5.08 cm (2 inches×2 inches) square.
[0128] In one or more embodiments, the glass-based article may exhibit a relative humidity of about 0.65 MPa·m 1 / 2 Or greater fracture toughness (K 1C In some cases, the fracture toughness may be about 0.69 MPa·m 1 / 2 or larger, about 0.7MPa·m 1 / 2 or larger, about 0.8MPa·m 1 / 2 or greater, or about 0.9MPa·m 1 / 2 In some embodiments, the fracture toughness may be in the following range: about 0.65 MPa·m 1 / 2 -About 1MPa·m 1 / 2 The fracture toughness values (K 1C ) refers to the value measured by the CNSB method described by Reddy, KPR et al. (Reddy, KPR et al., "Fracture Toughness Measurement of Glass and Ceramic Materials Using Chevron-Notched Specimens", J. Am. Ceram. Soc., 71[6], C-310-C-313 (1988)), except that Y* m Calculated using Equation 5 of Bubsey, RT et al. (Bubsey, RT et al., "Closed-Form Expressions for Crack-Mouth Displacement and Stress Intensity Factors for Chevron-Notched Short Bar and Short Rod Specimens Based on Experimental Compliance Measurements," NASA Technical Memorandum 83796, pp. 1-30 (October 1992).
[0129] In some embodiments, the substrate may also be characterized as having a HVN of about 500 to about 800 HVN (kgf / mm 2 ) (as measured by a Vickers hardness test with a 200 g load). In some embodiments, the glass-based article may include a Vickers hardness ranging from about 600 HVN to about 800 HVN.
[0130] The glass-based articles described herein may exhibit a stored tensile energy in the range of: greater than 0 J / m 2 -About 40J / m 2 In some cases, the stored tensile energy may be in the range of about 5 J / m 2 -About 40J / m 2 , about 10J / m 2 -About 40J / m 2 , about 15J / m 2 -About 40J / m 2 , about 20J / m 2 -About 40J / m 2 , about 1J / m 2 -About 35J / m 2 , about 1J / m 2 -About 30J / m 2 , about 1J / m 2 -About 25J / m 2 , about 1J / m 2 -About 20J / m 2 , about 1J / m 2 -About 15J / m 2 , about 1J / m 2 -About 10J / m 2 , about 10J / m 2 -About 30J / m 2 , about 10J / m 2 -About 25J / m 2 , about 15J / m 2 -About 30J / m 2 , about 15J / m 2 -About 25J / m 2 , about 18J / m 2 -About 22J / m 2 , about 25J / m 2 -About 40J / m 2 , or about 25 J / m 2 -About 30J / m 2 One or more embodiments of the thermally and chemically strengthened glass-based articles may exhibit a stored tensile energy of about 6 J / m 2 or greater, about 10J / m 2 or greater, about 15 J / m 2 or greater, or about 20 J / m 2 or larger.
[0131] The stored tensile energy can be calculated using the following equation (2):
[0132] Stored tensile energy (J / m 2)-[(1-v) / E]∫(σ^2)(dt) (2)
[0133] Where ν is Poisson's ratio, E is Young's modulus (in MPa), σ is stress (in MPa), and the integral is calculated over the entire thickness (in microns) of the tensile region only. The various Young's modulus values described herein refer to values measured by resonant ultrasonic spectroscopy techniques of the general type given in ASTM E2001-13 (ASTM E2001-13, entitled "Standard Guide for Resonant Ultrasound Spectroscopy for Defect Detection in Both Metallic and Non-metallic Parts").
[0134] The glass-based articles described herein generally have a Young's modulus of about 70 GPa or greater (e.g., in the range of about 70 GPa to about 100 GPa, about 72 GPa to about 100 GPa, about 75 GPa to about 100 GPa, about 76 GPa to about 100 GPa, about 78 GPa to about 100 GPa, about 79 GPa to about 100 GPa, about 80 GPa to about 100 GPa, about 81 GPa to about 100 GPa, about 82 GPa to about 100 GPa, about 83 GPa to about 100 GPa, about 86 GPa to about 100 GPa, about 88 GPa to about 100 GPa, about 89 GPa to about 100 GPa, about 81 GPa to about 100 GPa, about 80 GPa to about 1 GPa to about 100 GPa, about 80 GPa to about 100 GPa, about 82 GPa to about 100 GPa, about 84 GPa to about 100 GPa, about 86 GPa to about 100 GPa, about 88 GPa to about 100 GPa, about 90 GPa to about 100 GPa, about 70 GPa to about 95 GPa, about 70 GPa to about 90 GPa, about 70 GPa to about 88 GPa, about 70 GPa to about 86 GPa, about 70 GPa to about 85 GPa, about 70 GPa to about 84 GPa, about 70 GPa to about 82 GPa, or about 70 GPa to about 80 GPa). The Young's modulus is related to the composition of the glass-based article and can provide the final glass-based article with a desired stiffness, which is an extrinsic property.
[0135] In some embodiments, the glass-based article has a low liquidus viscosity, which allows the glass-based article to be formed by thin rolling technology. The term "liquidus viscosity" as used herein refers to the viscosity of molten glass at the liquidus temperature, wherein the term "liquidus temperature" refers to the temperature at which the molten glass is cooled from the melting temperature to the temperature at which the crystal first appears, or the temperature at which the last crystal melts when the temperature is raised from room temperature. In general, the liquidus viscosity of the glass-based article described herein (or the composition used to form such an article) is less than about 100 kilopoise (kP). In some embodiments, the glass-based article (or the composition used to form such an article) shows the following liquidus viscosity: less than about 80kP, less than about 60kP, less than about 40kP, less than about 30kP (e.g., about 15kP-about 30kP). The liquidus viscosity is determined by the following method. First, the liquidus temperature of the glass is measured according to ASTM C829-81 (2015), entitled "Standard Practice for Measurement of Liquidus Temperature of Glass by the Gradient Furnace Method". Second, the viscosity of the glass at the liquidus temperature is measured according to ASTM C965-96 (2012), entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point".
[0136] In one or more embodiments, the glass-based article has a Knoop Lateral Cracking Scratch Threshold in the range of about 4N to about 7N, about 4.5N to about 7N, about 5N to about 7N, about 4N to about 6.5N, about 4N to about 6N, or about 5N to about 6N. As used herein, the Knoop Lateral Cracking Scratch Threshold is the initiation of lateral cracking (3 or more of 5 scratch events). A series of increasing constant load scratches (minimum 3 / load, but more / load can be used to increase the confidence level) are performed to identify the Knoop Scratch Threshold. In the Knoop Scratch Lateral Cracking Threshold test, for each load, a sample of the glass substrate and / or article is scratched with a Knoop indenter at a speed of 0.25 mm / s over a length of more than 10 mm. The Knoop scratch threshold range is determined by comparing the test specimen to one of three failure modes: 1) multiple continuous transverse surface cracks exceeding two times the groove width, 2) damage in the groove, but multiple transverse surface cracks less than two times the groove width and visible damage, or 3) the presence of large subsurface transverse cracks greater than two times the groove width and / or a median crack at the scratch apex. The scratch threshold is the highest load that does not result in failure for three or more of the five events.
[0137] In one or more embodiments, the glass-based article exhibits a Vickers indentation fracture threshold in the range of: about 10 kgf (kilogram force) or greater, about 12 kgf or greater, or about 15 kgf or greater. In some cases, the glass-based article exhibits a Vickers indentation fracture threshold in the range of about 15 kgf-about 25 kgf. The Vickers indentation fracture threshold used herein is the start of the median / radial crack (3 or more of 5 indentation events) extending from at least one corner of the indentation site. In the Vickers indentation fracture threshold test, samples of glass substrates and articles are repeatedly indented with increasing loads using a diamond tip (at an angle of 136°). Each indentation has the potential to produce 4 radial cracks from one of the corners of the indentation. The average number of radial cracks at each indentation load is calculated, and the cracking threshold is the load (or 50% cracking threshold) when there are an average of 2 cracks / dents.
[0138] In one or more embodiments, the glass-based article exhibits improved surface strength when subjected to an Abraded Ring-on-Ring (AROR) test. The strength of a material is the stress at which rupture occurs. The AROR test is a surface strength measurement used to test flat glass specimens, and ASTM C1499-09 (2013), entitled "Standard Test Method for Monotonic Equibiaxial Flexural Strength of Advanced Ceramics at Ambient Temperature," serves as the basis for the AROR test method described herein. The entire contents of ASTM C1499-09 are incorporated herein by reference. In one embodiment, prior to the ring-on-ring test, the glass specimen is ground with 90 mesh silicon carbide (SiC) particles, which are delivered to the glass sample using the methods and apparatus described in Appendix A2 (entitled "Abrasion Procedures") of ASTM C158-02 (2012), entitled "Standard Test Methods for Strength of Glass by Flexure (Determination of Modulus of Rupture)". The entire contents of ASTM C158-09, especially Appendix A2, are incorporated herein by reference.
[0139] Prior to the ring-on-ring test, the surface of the glass-based article was ground as described in Appendix 2 of ASTM C158-02 using the apparatus shown in FIG. A2.1 of ASTM C158-02 to standardize and / or control the surface defect state of the sample. The rough material was typically blasted onto the surface 110 of the glass-based article using an air pressure of 304 kPa (44 psi) at a load of 15 psi; however, in the examples below, the rough material was blasted onto the surface 110 at other loads (e.g., 25 psi or 45 psi). After the air flow was established, a 5 cm 3 The ground material was poured into the funnel and after the introduction of the ground material, the sample was sandblasted for 5 seconds.
[0140] For the AROR test, a glass-based article having at least one ground surface 410 as shown in FIG. 5 is placed between two concentric rings of different sizes to determine the equilateral flexibility strength (i.e., the maximum stress that the material can withstand when undergoing buckling between two concentric rings), as shown in FIG. Figure 5In the AROR configuration 400, a ground glass-based article 410 is supported by a support ring 420 having a diameter D2. A force F is applied to the surface of the glass-based article via a load ring 430 having a diameter D1 by a dynamometer (not shown).
[0141] The ratio of the diameters of the load ring to the support ring, D1 / D2, may be about 0.2-0.5. In some embodiments, D1 / D2 is about 0.5. The load ring and support rings 130, 120 should be coaxially aligned within 0.5% of the support ring diameter D2. The dynamometer used for testing should be accurate to within ±1% of the selected range at any load. In some embodiments, testing is conducted at a temperature of 23±2°C and a relative humidity of 40±10%.
[0142] For fixture design, the radius r of the protruding surface of the load ring 430 is h / 2≤r≤3h / 2, where h is the thickness of the glass-based article 410. The load ring and support rings 430, 420 are generally made of a hardness HR c Made of hardened steel >40. AROR fixtures are commercially available.
[0143] The target failure mechanism of the AROR test is to observe the fracture of the glass-based product 410 originating from the surface 430a within the load ring 430. For data analysis, failures existing outside this area (i.e., between the load ring 430 and the support ring 420) are ignored. However, due to the thinness and high strength of the glass-based product 410, large deflections exceeding 1 / 2 of the specimen thickness h are sometimes observed. Therefore, it is not abnormal to observe a high percentage of failures originating from below the load ring 430. It is impossible to accurately calculate stress without understanding the stress development and failure sources within and under the ring of each specimen (collected by strain gauge analysis). Therefore, the AROR test focuses on the peak load of failure when measuring the response.
[0144] The strength of glass-based articles depends on the presence of surface flaws. However, it is not possible to accurately predict the likelihood of the presence of a flaw of a given size, as the strength of glass is statistical in nature. Therefore, a probability distribution is generally used as a statistical representation of the data obtained.
[0145] In some embodiments, the surface or equilateral flexible strength of the glass-based articles described herein is 20 kgf or greater, and up to about 30 kgf, measured by the AROR test using a load of 25 psi or even 45 psi to abrade the surface. In other embodiments, the surface strength is 25 kgf or more, and in other embodiments, 30 kgf or more.
[0146] In some embodiments, the glass-based articles described herein may be described in terms of performance in an inverted ball on sandpaper (IBoS) test. The IBoS test is a dynamic component level test that simulates the primary mechanism of failure caused by damage induction plus bending common in glass-based articles used in mobile or handheld electronic devices, such as Figure 6 In the field, damage introduction occurs on the top surface of the glass-based article ( Figure 7 a). The fracture initiates at the top surface of the glass-based article and the damage penetrates into the glass-based article ( Figure 7 b), or, the fracture propagates from the top surface of the glass-based article or from an inner portion thereof ( Figure 7 c). The IBoS test is designed to simultaneously introduce damage to the surface of the glass and impose bending under dynamic load. In some cases, when it includes compressive stress, the glass-based article shows improved drop performance compared to the same glass-based article that does not include compressive stress.
[0147] IBoS test equipment such as Figure 6 As shown schematically. The apparatus 500 includes a test stand 510 and a ball 530. The ball 530 is a rigid ball or a solid ball, such as a stainless steel ball, etc. In one embodiment, the ball 530 is a 4.2 gram stainless steel ball having a diameter of 10 mm. The ball 530 is dropped directly onto the glass-based product sample 518 from a predetermined height h. The test stand 510 includes a solid base 512, which comprises a hard rigid material, such as granite, etc. A sheet 514 having an abrasive material arranged on the surface is placed on the upper surface of the solid base 512, so that the surface with the abrasive material faces upward. In some embodiments, the sheet 514 is sandpaper having a 30 mesh surface (and in other embodiments, a 180 mesh surface). The glass-based product sample 518 is appropriately fixed to the sheet 514 by a sample holder 515, so that there is an air gap 516 between the glass-based product sample 518 and the sheet 514. The air gap 516 between the sheet 514 and the glass-based product sample 518 allows the glass-based product sample 518 to bend and bend onto the ground surface of the sheet 514 after being impacted by the ball 530. In one embodiment, the glass-based product sample 218 is clamped at all corners to keep it contained only at the point of ball impact and to ensure repeatability. In some embodiments, the sample holder 514 and the test holder 510 are suitable for accommodating sample thicknesses of up to about 2 mm. The air gap 516 is about 50-100 μm. The air gap 516 is adapted to adjust for differences in material stiffness (Young's modulus, Emod), but also includes Young's modulus and thickness of the sample. An adhesive strip 520 can be used to cover the upper surface of the glass-based product sample to collect fragments of the glass-based product sample 518 in the event of a breakage after impact with the ball 530.
[0148] A variety of materials can be used as the grinding surface. In a specific embodiment, the grinding surface is sandpaper, such as silicon carbide or aluminum oxide sandpaper, engineering sandpaper, or any abrasive material known to those skilled in the art with considerable hardness and / or sharpness. In some embodiments, 30-grit sandpaper can be used because it has a more consistent surface topography than concrete or asphalt, and a particle size and sharpness that produces the desired level of specimen surface damage.
[0149] In one aspect, Figure 8 A method 600 for performing an IBoS test using the apparatus 500 described above is shown. In step 610, a glass-based article sample ( Figure 6 218) is placed in the test holder 510 described above and fixed in the sample holder 515 so that an air gap 516 is formed between the glass-based product sample 518 and the sheet 514 having an abrasive surface. The method 600 assumes that the sheet 514 having an abrasive surface has been placed in the test holder 510. However, in some embodiments, the method may include placing the sheet 514 in the test holder 510 so that the surface having the abrasive material faces upward. In some embodiments (step 610a), before the glass-based product sample 518 is fixed in the sample holder 510, an adhesive strip 520 is applied to the upper surface of the glass-based product sample 518.
[0150] In step 520, a solid ball 530 having a predetermined mass and size is dropped from a predetermined height h onto the upper surface of the glass-based article sample 518, such that the ball 530 impacts the upper surface (or the adhesive strip 520 adhered to the upper surface) at the approximate center of the upper surface (e.g., within 1 mm, or within 3 mm, or within 5 mm, or within 10 mm of the center). After the impact in step 520, the extent of damage to the glass-based article sample 518 is determined (step 630). As described above, the term "fracture" herein refers to cracks that propagate through the entire thickness and / or the entire surface of a substrate when an object is dropped or impacted on the substrate.
[0151] In method 600, sheet 518 having an abrasive surface may be replaced after each drop to avoid "aging" effects that have been observed with repeated use of other types of drop test surfaces (eg, concrete or asphalt).
[0152] Various predetermined drop heights h and increments are typically used in method 600. For example, a minimum drop height (e.g., about 10-20 cm) may be used at the beginning of the test. Then, for successive drops, the height may be increased in fixed increments or in varying increments. Once the glass-based article sample 518 breaks or cracks, the test in method 600 is stopped (step 631). Alternatively, if the drop height h reaches a maximum drop height (e.g., about 100 cm) without cracking, the drop test method 300 may also be stopped, or step 520 may be repeated at the maximum height until cracking occurs.
[0153] In some embodiments, the IBoS test of method 600 is performed only once for each glass-based article sample 518 at each predetermined height h. However, in other embodiments, multiple tests may be performed for each sample at each height.
[0154] If the glass-based article sample 518 breaks ( Figure 8 If no rupture is observed due to the falling ball at the predetermined drop height (step 632), the drop height is increased by predetermined increments (step 634), such as 5, 10, or 20 cm, and steps 620 and 630 are repeated until sample rupture is observed (631) or the maximum test height is reached (636) without sample rupture. When step 631 or 636 is reached, the test method 600 is terminated.
[0155] When subjected to the Inverted Ball on Sandpaper (IBoS) test described above, embodiments of the glass-based articles described herein have a survival rate of about 60% or more when the ball is dropped from a height of 100 cm onto a glass surface. For example, if three of five identical (or nearly identical) samples (i.e., having approximately the same composition and approximately the same compressive stress and compression depth or compressive stress layer depth after strengthening, as described herein) pass the IBoS drop test without breaking when dropped from a given height (here, 100 cm), the glass-based article is described as having a survival rate of 60%. In other embodiments, the survival rate of the strengthened glass-based article in the 80 cm IBoS test is about 70% or more, in other embodiments, about 80% or more, and in other embodiments, about 90% or more. In other embodiments, the survival rate of the strengthened glass-based article dropped from a height of 100 cm in the IBoS test is about 60% or more, in other embodiments, about 70% or more, in other embodiments, about 80% or more, in other embodiments, about 90% or more. In one or more embodiments, the survival rate of the strengthened glass-based article dropped from a height of 150 cm in the IBoS test is about 60% or more, in other embodiments, about 70% or more, in other embodiments, about 80% or more, in other embodiments, about 90% or more.
[0156] In order to determine the survivability of a glass-based article when dropped from a predetermined height using the IBoS test method and apparatus described above, at least 5 identical (or approximately identical) samples of the glass-based article (i.e., having approximately the same composition and, if strengthened, approximately the same compressive stress and compression depth or layer depth) are tested, although a greater number (e.g., 10, 20, 30, etc.) of samples may be tested to increase the confidence level of the test results. Each sample is dropped a single time from a predetermined height (e.g., 100 cm or 150 cm), or is dropped from increasing heights without breaking until the predetermined height is reached and visually (i.e., with the naked eye) inspected for evidence of breakage (crack formation and propagation through the entire thickness of the sample and / or across the surface of the sample). If no breakage is observed after dropping from the predetermined height, the sample is considered to have "passed" the drop test, and if breakage is observed when the sample is dropped from a height less than or equal to the predetermined height, the sample is considered to have "failed" (or "failed") the drop test. The survivability rate is determined as a percentage of the number of samples that passed the drop test. For example, if 7 samples out of a set of 10 samples do not break when dropped from a predetermined height, the survivability rate of the glass would be 70%.
[0157] The glass-based articles described herein can be transparent. In one or more embodiments, the glass-based articles can have a thickness of about 3 mm or less, such as 1 mm or less, and exhibit a transmittance of about 88% or more over a wavelength range of about 380 nm to about 780 nm.
[0158] The glass-based article may also display substantially white. For example, the glass-based article may display CIELAB chromaticity space coordinates under CIE illuminant F02: L* value greater than or equal to about 88, a* value from about -3 to about +3, and b* value from about -6 to about +6. Alternatively, the glass-based article may display CIELAB chromaticity space coordinates under CIE illuminant F02: L* value less than or equal to about 40, a* value from about -3 to about +3, and b* value from about -6 to about +6. The chromaticity space coordinates may exist under other CIE illuminants (e.g., D65).
[0159] The choice of substrate is not particularly limited. In some examples, the glass-based article can be described as having a high cation diffusivity for ion exchange. In one or more embodiments, the glass or glass-ceramic has a fast ion exchange capability, that is, the glass or glass-ceramic exhibits a monovalent ion diffusivity of about 450 μm at 460°C. 2 / hour or more, or about 500 μm at 460°C 2 / hour or more. In one or more embodiments, the glass or glass-ceramic exhibits a sodium ion diffusion rate of about 450 μm at 460°C. 2 / hour or more, or about 500 μm at 460°C 2 / hour or more. In one or more embodiments, the glass or glass-ceramic exhibits a potassium ion diffusion rate of about 450 μm at 460°C. 2 / hour or more, or about 500 μm at 460°C 2 / hour or more.
[0160] The glass-based article may include an amorphous substrate, a crystalline substrate, or a combination thereof (e.g., a glass-ceramic substrate). In one or more embodiments, the glass-based article substrate (before being chemically strengthened as described herein) may include a glass composition, in mole percent (mol %), comprising:
[0161] SiO2, ranging from about 40 to about 80, Al2O3, ranging from about 10 to about 30, B2O3, ranging from about 0 to about 10, R2O, ranging from about 0 to about 20, and RO, ranging from about 0 to about 15. As used herein, R2O refers to the total amount of alkali metal oxides (e.g., Li2O, Na2O, K2O, Rb2O, and Cs2O). As used herein, RO refers to the total amount of alkaline earth metal oxides (e.g., MgO, CaO, SrO, BaO, ZnO, etc.). In some cases, the composition may include one or both of ZrO2 ranging from about 0 mol% to about 5 mol% and P2O5 ranging from about 0 to about 15 mol%. TiO2 may be present at about 0 mol% to about 2 mol%.
[0162] In some embodiments, the glass composition may include SiO2 in an amount, in mol%, ranging from about 45 to about 80, about 45 to about 75, about 45 to about 70, about 45 to about 65, about 45 to about 60, about 45 to about 65, about 45 to about 65, about 50 to about 70, about 55 to about 70, about 60 to about 70, about 70 to about 75, about 70 to about 72, or about 50 to about 65.
[0163] In some embodiments, the glass composition may include Al2O3 in an amount, in mol%, ranging from about 5 to about 28, about 5 to about 26, about 5 to about 25, about 5 to about 24, about 5 to about 22, about 5 to about 20, about 6 to about 30, about 8 to about 30, about 10 to about 30, about 12 to about 30, about 12 to about 18, or about 12 to about 14.
[0164] In one or more embodiments, the glass composition may include B2O3 in an amount, in mol%, ranging from about 0 to about 8, about 0 to about 6, about 0 to about 4, about 0.1 to about 8, about 0.1 to about 6, about 0.1 to about 4, about 1 to about 10, about 2 to about 10, about 4 to about 10, about 2 to about 8, about 0.1 to about 5, or about 1 to about 3. In some cases, the glass composition may be substantially free of B2O3. As used herein, the phrase "substantially free" when referring to a component of the composition means that the component is not actively or intentionally added to the composition during initial batching, but may be present as an impurity in an amount less than about 0.001 mol%.
[0165] In some embodiments, the glass composition may include one or more alkaline earth oxides, such as MgO, CaO, and ZnO. In some embodiments, the total amount of the one or more alkaline earth oxides may be a non-zero amount, up to about 15 mol%. In one or more specific embodiments, the total amount of any of the alkaline earth oxides may be a non-zero amount up to about 14 mol%, up to about 12 mol%, up to about 10 mol%, up to about 8 mol%, up to about 6 mol%, up to about 4 mol%, up to about 2 mol%, or up to about 1.5 mol%. In some embodiments, the total amount of the one or more alkaline earth oxides, in mol%, may be in the following ranges: about 0.1-10, about 0.1-8, about 0.1-6, about 0.1-5, about 1-10, about 2-10, or about 2.5-8. The amount of MgO may be in the following range: about 0 mol% to about 5 mol% (e.g., about 2 mol% to about 4 mol%). The amount of ZnO may range from about 0 to about 2 mol% (e.g., about 0.1 mol% to about 2 mol%, about 0.1 mol% to about 1 mol%, or about 0.5 mol% to about 1.5 mol%). The amount of CaO may range from about 0 mol% to about 2 mol%. In one or more embodiments, the glass composition may include MgO and may be substantially free of CaO and ZnO. In a variation, the glass composition may include any one of CaO or ZnO and may be substantially free of the other of MgO, CaO, and ZnO. In one or more specific embodiments, the glass composition may include only two of the alkaline earth metal oxides MgO, CaO, and ZnO, and may be substantially free of the third of the metal oxides.
[0166] The total amount of alkali metal oxide, R2O, in the glass composition, in mol %, may be in the range of about 5 to about 20, about 5 to about 18, about 5 to about 16, about 5 to about 15, about 5 to about 14, about 5 to about 12, about 5 to about 10, about 5 to about 8, about 5 to about 20, about 6 to about 20, about 7 to about 20, about 8 to about 20, about 8 to about 18, about 8 to about 16, about 8 to about 14, about 8 to about 12, or about 8 to about 11.
[0167] In one or more embodiments, the glass composition includes Na2O in an amount ranging from about 0 mol% to about 18 mol%, about 0 mol% to about 16 mol%, or about 0 mol% to about 14 mol%, about 0 mol% to about 12 mol%, about 1 mol% to about 18 mol%, about 1 mol% to about 16 mol%, about 1 mol% to about 14 mol%, about 1 mol% to about 12 mol%, about 1 mol% to about 10 mol%, about 1 mol% to about 8 mol%, about 1 mol% to about 5 mol%, about 1 mol% to about 4 mol%, or about 1 mol% to about 3 mol%. In some embodiments, the composition may include less than about 4 mol% Na2O.
[0168] In some embodiments, the amounts of Li2O and Na2O are controlled at specific amounts or ratios to balance formability and ion exchangeability. For example, as the amount of Li2O increases, the liquidus viscosity may decrease, thereby preventing some forming methods from being used; however, such glass compositions are ion exchanged to deeper DOC levels as described herein. The amount of Na2O can adjust the liquidus viscosity, but may inhibit ion exchange to deeper DOC levels. In one or more embodiments, to achieve sufficient stress at depth in glass compositions containing Li2O (or those compositions in which exchange of Li+ with Na+ is the primary strengthening mechanism), the glass compositions of one or more embodiments include a Li2O / (R2O) ratio greater than about 0.3, about 0.45 or greater, about 0.5 or greater, or about 0.7 or greater. In order to maintain higher CS values at greater depths in the glass-based articles described herein, especially those glass-based articles including Na2O (or those compositions in which exchange of Na+ with K+ is the primary strengthening mechanism), the glass compositions of one or more embodiments may include a Na2O / (R2O) ratio of greater than about 0.3, about 0.5 or greater, or about 0.7 or greater.
[0169] In one or more embodiments, the glass composition may include K2O in an amount of less than about 5 mol%, less than about 4 mol%, less than about 3 mol%, less than about 2 mol%, or less than about 1 mol%. In one or more alternative embodiments, the glass composition may be substantially free (as defined herein) of K2O.
[0170] In one or more embodiments, the glass composition may include Li2O in an amount of about 0 mol% to about 18 mol%, about 0 mol% to about 15 mol%, or about 0 mol% to about 10 mol%, about 0 mol% to about 8 mol%, about 0 mol% to about 6 mol%, about 0 mol% to about 4 mol%, or about 0 mol% to about 2 mol%. In some embodiments, the glass composition may include Li2O in an amount of about 2 mol% to about 10 mol%, about 4 mol% to about 10 mol%, about 6 mol% to about 10 mol%, or about 5 mol% to about 8 mol%. In one or more alternative embodiments, the glass composition may be substantially free (as defined herein) of Li2O.
[0171] In one or more embodiments, the glass composition may include Fe2O3. In such embodiments, Fe2O3 may be present in an amount of less than about 1 mol%, less than about 0.9 mol%, less than about 0.8 mol%, less than about 0.7 mol%, less than about 0.6 mol%, less than about 0.5 mol%, less than about 0.4 mol%, less than about 0.3 mol%, less than about 0.2 mol%, less than about 0.1 mol% and all ranges and subranges therebetween. In one or more alternative embodiments, the glass composition may be substantially free (as defined herein) of Fe2O3.
[0172] In one or more embodiments, the glass composition may include ZrO2. In such embodiments, ZrO2 may be present in an amount of less than about 1 mol%, less than about 0.9 mol%, less than about 0.8 mol%, less than about 0.7 mol%, less than about 0.6 mol%, less than about 0.5 mol%, less than about 0.4 mol%, less than about 0.3 mol%, less than about 0.2 mol%, less than about 0.1 mol% and all ranges and subranges therebetween. In one or more alternative embodiments, the glass composition may be substantially free (as defined herein) of ZrO2.
[0173] In one or more embodiments, the glass composition may include PO in the range of about 0 mol% to about 10 mol%, about 0 mol% to about 8 mol%, about 0 mol% to about 6 mol%, about 0 mol% to about 4 mol%, about 0.1 mol% to about 10 mol%, about 0.1 mol% to about 8 mol%, about 2 mol% to about 8 mol%, about 2 mol% to about 6 mol%, or about 2 mol% to about 4 mol%. In some cases, the glass composition may be substantially free of PO.
[0174] In one or more embodiments, the glass composition may include TiO2. In such embodiments, TiO2 may be present in an amount of less than about 6 mol%, less than about 4 mol%, less than about 2 mol%, or less than about 1 mol%. In one or more alternative embodiments, the glass composition may be substantially free (as defined herein) of TiO2. In some embodiments, TiO2 is present in an amount ranging from about 0.1 mol% to about 6 mol%, or from about 0.1 mol% to about 4 mol%.
[0175] In some embodiments, the glass composition may include various ratios. For example, the glass composition may include a ratio of Li2O (in mol %) to the total amount of R2O (in mol %) ranging from about 0 to about 1, about 0.4 to about 1, about 0.45 to about 1, about 0.5 to about 1, or about 0.6 to about 1.
[0176] In some embodiments, the glass composition may include a difference between the total amount of R2O (in mol %) and the amount of Al2O3 (in mol %) (R2O-Al2O3) ranging from about -5 to about 2 (e.g., about -5 to about 1.5, about -5 to about 1, about -5 to about 0, about -5 to about -1, about -5 to about -2, about -4 to about 2, about -3 to about 2, about -2 to about 2, or about -3 to about -1).
[0177] In some embodiments, the glass composition may include R x The difference between the total amount of O (in mol %) and the amount of Al2O3 (in mol %) is as follows (R x O-Al2O3): ranges from about 0 to about 5 (e.g., about 0 to about 4, about 0 to about 3, about 0.1 to about 4, about 0.1 to about 3, about 1 to about 3, or about 1 to about 2). As used herein, RxO includes R2O and RO, as defined herein.
[0178] In some embodiments, the glass composition may include a ratio of the total amount of R2O (in mol %) to the amount of Al2O3 (in mol %) (R2O / Al2O3) ranging from about -4 to about 5, from about -2 to about 4, or from about 0.1 to about 5. For example, the ratio of the total amount of R2O (in mol %) to the amount of Al2O3 (in mol %) (R2O / Al2O3) may range from about -4 to about 4.5, from about -4 to about 4, from about -4 to about 3.5, from about -4 to about 3, from about -4 to about 2.5, from about -4 to about 2, from about -4 to about 1.5, from about -4 to about 1, from about -3.5 to about 5, from about -3 to about 5, from about -2.5 to about 5, from about -2 to about 5, from about -1.5 to about 5, from about -1 to about 5, from about 0 to about 5, from about 0 to about 5, from about 0 to about 4, from about 0 to about 3, from about 0.1 to about 4, from about 0.1 to about 3, or from about 0.1 to about 2.
[0179] In one or more embodiments, the glass composition includes a combined amount of Al2O3 and Na2O of about 15 mol% or less (e.g., 14 mol% or less, 13 mol% or less, 12 mol% or less, 11 mol% or less, or about 10.5 mol% or less). The combined amount of Al2O3 and Na2O may be greater than about 5 mol%.
[0180] The glass compositions of one or more embodiments may exhibit a ratio of the amount of MgO (in mol %) to the total amount of RO (in mol %) ranging from about 0 to about 1. In some embodiments, the MgO / RO ratio ranges from about 0 to about 0.9, from about 0 to about 0.8, from about 0 to about 0.7, from about 0 to about 0.6, from about 0 to about 0.5, from about 0.1 to about 1, from about 0.2 to about 1, from about 0.3 to about 1, from about 0.4 to about 1, or from about 0.5 to about 1.
[0181] In some embodiments, the glass composition may be substantially free of nucleating agents. Typical examples of nucleating agents are TiO2, ZrO2, etc. Nucleating agents can be described in a functional manner, wherein a nucleating agent is a component in the glass that is capable of initiating the formation of crystallites in the glass.
[0182] In some embodiments, the composition for the glass substrate may be batch treated with about 0 mol% to about 2 mol% of at least one fining agent selected from any one or more of Na2SO4, NaCl, NaF, NaBr, K2SO4, KCl, KF, KBr, As2O3, Sb2O3, and SnO2. The glass composition according to one or more embodiments may further include SnO2 in a range of about 0 to about 2, about 0 to about 1, about 0.1 to about 2, about 0.1 to about 1, or about 1 to about 2. The glass compositions described herein may be substantially free of As2O3 and / or Sb2O3.
[0183] In one or more embodiments, the composition may specifically include 62 mol%-75 mol% SiO2; 10.5 mol%-about 17 mol% Al2O3; 5 mol%-about 13 mol% Li2O; 0 mol%-about 4 mol% ZnO; 0 mol%-about 8 mol% MgO; 2 mol%-about 5 mol% TiO2; 0 mol%-about 4 mol% B2O3; 0 mol%-about 5 mol% Na2O; 0 mol%-about 4 mol% K2O; 0 mol%-about 2 mol% ZrO2; 0 mol%-about 7 mol% P2O5; 0 mol%-about 0.3 mol% Fe2O3; 0 mol%-about 2 mol% MnOx; and 0.05 mol%-about 0.2 mol% SnO2.
[0184] In one or more embodiments, the composition may include 67 mol% to about 74 mol% SiO2; 11 mol% to about 15 mol% Al2O3; 5.5 mol% to about 9 mol% Li2O; 0.5 mol% to about 2 mol% ZnO; 2 mol% to about 4.5 mol% MgO; 3 mol% to about 4.5 mol% TiO2; 0 mol% to about 2.2 mol% B2O3; 0 mol% to about 1 mol% Na2O; 0 mol% to about 1 mol% K2O; 0 mol% to about 1 mol% ZrO2; 0 mol% to about 4 mol% P2O5; 0 mol% to about 0.1 mol% Fe2O3; 0 mol% to about 1.5 mol% MnOx; and 0.08 mol% to about 0.16 mol% SnO2.
[0185] In one or more embodiments, the composition may include 70 mol% to 75 mol% SiO2; 10 mol% to about 15 mol% Al2O3; 5 mol% to about 13 mol% Li2O; 0 mol% to about 4 mol% ZnO; 0.1 mol% to about 8 mol% MgO; 0 mol% to about 5 mol% TiO2; 0.1 mol% to about 4 mol% B2O3; 0.1 mol% to about 5 mol% Na2O; 0 mol% to about 4 mol% K2O; 0 mol% to about 2 mol% ZrO2; 0 mol% to about 7 mol% P2O5; 0 mol% to about 0.3 mol% Fe2O3; 0 mol% to about 2 mol% MnOx; and 0.05 mol% to about 0.2 mol% SnO2.
[0186] As described herein, other exemplary compositions of glass-based articles prior to chemical strengthening are shown in Table 1. Table 1B lists selected physical properties determined from the examples listed in Table 1A. The physical properties listed in Table 1B include: density; low and high temperature CTE; strain point, annealing point and softening point; 10 11Poisson's ratio; Young's modulus; refractive index; and strain optical coefficient. In some embodiments, the glass-based articles and glass substrates described herein have a high temperature CTE less than or equal to 30 ppm / °C and / or a Young's modulus greater than or equal to 70 GPa, and in some embodiments, a Young's modulus as high as 80 GPa.
[0187] Table 1A: Exemplary compositions prior to chemical strengthening.
[0188] Mol% Example A Example B Example C Example D Example E Example F <![CDATA[SiO2]]> 71.8 69.8 69.8 69.8 69.8 69.8 <![CDATA[Al2O3]]> 13.1 13 13 13 13 13 <![CDATA[B2O3]]> 2 2.5 4 2.5 2.5 4 <![CDATA[Li2O]]> 8 8.5 8 8.5 8.5 8 MgO 3 3.5 3 3.5 1.5 1.5 ZnO 1.8 2.3 1.8 2.3 2.3 1.8 <![CDATA[Na2O]]> 0.4 0.4 0.4 0.4 0.4 0.4 <![CDATA[TiO2]]> 0 0 0 1 1 1 <![CDATA[Fe2O3]]> 0 0 0 0.8 0.8 0.8 <![CDATA[SnO2]]> 0.1 0.1 0.1 0.1 0.1 0.1
[0189]
[0190] Table 1B. Selected physical properties of Example GL.
[0191]
[0192]
[0193] *Indicates glass substrate properties measured before strengthening.
[0194] Table 1C shows the properties of Example H after ion exchange in a molten salt bath having 80% KNO3 and 20% NaNO3 and a temperature of 430°C for 16 hours.
[0195] Table 1C: Properties of Example H after ion exchange for 16 hours in a molten salt bath comprising 80% KNO3 and 20% NaNO3, with a temperature of 430°C.
[0196]
[0197] *Indicates glass substrate properties measured before strengthening.
[0198] When the glass-based article comprises a glass-ceramic, the crystalline phase may comprise beta-spodumene, rutile, gahnite, or other known crystalline phases, and combinations thereof.
[0199] The glass-based article can be substantially flat, but other embodiments may employ curved or any other shaped or contoured substrates. In some cases, the glass-based article can have a 3D or 2.5D shape. The glass-based article can be substantially optically clear, transparent, and free of light scattering. The glass-based article can have a refractive index of about 1.45-1.55. As used herein, refractive index values are relative to a wavelength of 550 nm.
[0200] Additionally or alternatively, the thickness of a glass-based article may be constant along one or more dimensions, or may vary along one or more dimensions thereof for aesthetic and / or functional reasons. For example, the edges of a glass-based article may be thicker than a more central region of the glass-based article. Depending on the application or use of the article, the length, width, and thickness dimensions of a glass-based article may also vary.
[0201] Glass-based articles are characterized by the manner in which they are formed. For example, glass-based articles can be characterized as float-formable (i.e., formed by a float process), down-drawable, specifically, fusion-formable, or slot-drawable (i.e., formed by a down-draw process such as a fusion draw process or a slot draw process).
[0202] The glass-based products that can be formed by the float process can be characterized as the smooth surface and uniform thickness obtained by floating the molten glass on a bed of molten metal (usually tin). In an exemplary process, the molten glass is fed onto the surface of the molten tin bed to form a floating glass ribbon. As the glass ribbon flows along the tin bath, the temperature gradually decreases until the glass ribbon solidifies into a solid glass-based product, which can be lifted from the tin onto a roller. Once leaving the bath, the glass-based product can be further cooled and annealed to reduce internal stress. When the glass-based product is a glass-ceramic, the glass-based product formed by the float process can be subjected to a ceramicization process, by which one or more crystalline phases are produced.
[0203] The down-drawing method produces a glass-based product with uniform thickness, which has a relatively original surface. Because the average flexural strength of the glass-based product is controlled by the amount and size of the surface defects, the original surface with the smallest contact has a higher initial strength. When the high-strength glass-based product is subsequently further strengthened (e.g., chemically strengthened), the resulting strength can be higher than the strength of the glass-based product whose surface has been polished and polished. The down-drawn glass-based product can be drawn to a thickness of less than about 2 mm. In addition, the down-drawn glass-based product has a very flat and smooth surface, so that it can be used for its final application without costly grinding and polishing. When the glass-based product is a glass-ceramic, the glass-based product formed by the down-drawing process can be subjected to a ceramicization process, by which one or more crystalline phases are produced.
[0204] The fusion drawing method uses, for example, a drawing tank having a channel for receiving molten glass raw materials. The channel has a weir, which is open at the top of both sides of the channel along the length of the channel. When the channel is filled with molten material, the molten glass overflows from the weir. Under the action of gravity, the molten glass flows down from the outer surface of the drawing tank as two flowing glass films. The outer surfaces of these drawing tanks extend downward and inward so that they are combined at the edge below the drawing tank. The two flowing glass films are combined at the edge to fuse and form a single flowing glass-based product. The advantage of the fusion drawing method is that since the two glass films overflowing from the channel are fused together, any outer surface of the resulting glass-based product is not in contact with any part of the equipment. Therefore, the surface properties of the glass-based product of the fusion drawing are not affected by such contact. When the glass-based product is glass-ceramic, the glass-based product formed by the fusion process can be subjected to a ceramicization process, by which one or more crystalline phases are produced.
[0205] The slot draw process is different from the fusion draw process. In the slot draw process, molten raw material glass is provided to a drawing tank. The bottom of the drawing vessel has an open slot with a nozzle extending along the length of the slot. The molten glass flows through the slot / nozzle and is drawn down as a continuous glass-based article and enters an annealing zone. When the glass-based article is a glass-ceramic, the glass-based article formed by the slot draw process can be subjected to a ceramization process by which one or more crystalline phases are produced.
[0206] In some embodiments, the glass-based product can be formed using a thin rolling process, such as described in U.S. Patent No. 8,713,972, entitled “Precision Glass Roll Forming Process and Apparatus,” U.S. Patent No. 9,003,835, entitled “Precision Roll Forming of Textured Sheet Glass,” U.S. Patent Publication No. 20150027169, entitled “Methods And Apparatus For Forming A Glass Ribbon,” and U.S. Patent Publication No. 20050099618, entitled “Apparatus and Method for Forming Thin Glass Products,” which are incorporated herein by reference in their entirety. More specifically, a glass-based article can be formed by providing a vertical molten glass flow, forming the provided molten glass flow or glass-ceramic using a pair of forming rollers, the surface temperature of the forming rollers being maintained at about 500° C. or higher or about 600° C. or higher to form a shaped glass ribbon having a formed thickness, and adjusting the size of the shaped glass ribbon using a pair of sizing rollers, the surface temperature of the sizing rollers being maintained at about 400° C. or lower to produce a glass ribbon of a certain size having a desired thickness less than the formed thickness and a desired thickness uniformity. An apparatus for forming a glass ribbon may include a glass feeding device for providing a supplied molten glass flow; a pair of forming rollers whose surface temperature is maintained at about 500°C or higher, the forming rollers are closely spaced from each other, and a glass forming gap is formed between the forming rollers, wherein the glass forming gap is located vertically below the glass feeding device, and is used to receive the supplied molten glass flow and dilute the supplied molten glass flow between the forming rollers to form a formed glass ribbon with a formed thickness; and a pair of sizing rollers whose surface temperature is maintained at about 400°C or lower, the sizing rollers are closely spaced from each other, and a glass sizing gap is formed between the sizing rollers, wherein the glass sizing gap is located vertically below the forming rollers, and is used to receive the formed glass ribbon and thin the formed glass ribbon to produce a glass ribbon of a certain size with a desired thickness and a desired thickness uniformity.
[0207] In some cases, thin rolling processes may be employed where the viscosity of the glass does not permit the use of fusion or slot drawing methods. For example, thin rolling may be utilized to form glass-based articles when the glass exhibits a liquidus viscosity of less than 100 kP.
[0208] Glass-based articles may be acid polished or treated in any other manner to remove or reduce the effects of surface imperfections.
[0209] Another aspect of the present application relates to devices comprising the glass-based articles described herein. For example, the device may include any device having a display screen or thin glass that requires strengthening. In one or more embodiments, the device is an electronic device, which may include a mobile device, such as a mobile phone, a laptop computer, a tablet computer, an mp3 player, a navigator, etc., or a fixed device, such as a computer, an electronic display, an in-vehicle information / entertainment system, a billboard, a point-of-sale system, a navigation system, etc.). In some embodiments, the glass-based articles described herein may be integrated into buildings (walls, fixtures, panels, windows, etc.), transportation products (e.g., the surface or interior surface of glass in automotive applications, trains, aircraft, ships, etc.), appliances (e.g., washers, dryers, dishwashers, refrigerators, etc.), or any product that requires some crack resistance. As Fig.39 As shown, an electronic device 1000 may include a glass-based article 100 according to one or more embodiments described herein. The device 100 includes a housing 1020 having a front surface 1040, a rear surface 1060, and a side surface 1080; electronic components (not shown) at least partially or completely located inside the housing and including at least one controller, a memory, and a display screen 1120 located at or near the front surface of the housing. The glass-based article 100 is shown as a cover disposed at or above the front surface of the housing, so that it is located above the display screen 1120. In some embodiments, the glass-based article can be used as a bottom cover.
[0210] Another aspect of the present invention pertains to a method of forming a crack-resistant glass-based article. The method includes providing a glass-based substrate having a first surface and a second surface, the first surface and the second surface defining a thickness of less than or equal to about 3 mm or less, for example, 1 mm or less, and generating a stress profile in the glass-based substrate as described herein to provide a crack-resistant glass-based article. In one or more embodiments, generating the stress profile includes ion-exchanging a plurality of alkali ions into the glass-based substrate to form a non-zero alkali metal oxide concentration that varies along a majority of the thickness (as described herein) or along the entire thickness. In one example, generating the stress profile includes immersing the glass-based substrate in a molten salt bath comprising a nitrate of Na+, K+, Cs+, or a combination thereof, at a temperature greater than or equal to about 350°C (e.g., about 350-500°C). In one example, the molten bath may include NaNO3, KNO3, or a combination thereof, and the temperature may be about less than or equal to 485°C. In another example, the bath treatment may include a mixture of NaNO3 and KNO3 and have a temperature of about 460°C. The glass-based substrate can be immersed in the bath for about 2 hours or more, up to about 48 hours (e.g., about 2 hours to about 10 hours, about 2 hours to about 8 hours, about 2 hours to about 6 hours, about 3 hours to about 10 hours, or about 3.5 hours to about 10 hours).
[0211] In some embodiments, the method may include chemically strengthening or ion exchanging a glass-based substrate in a single bath or in multiple steps using sequential immersion steps in multiple baths. For example, two or more baths may be used in sequence. The composition of the one or more baths may include a single metal (e.g., Ag+, Na+, K+, Rb+, or Cs+), or a combination of metals in the same bath. When more than one bath is used, the baths may have the same or different compositions and / or temperatures from one another. The immersion time in each such bath may be the same or may vary to provide the desired stress profile.
[0212] In one or more embodiments of the method, a second bath or a subsequent bath may be used to produce a larger surface CS. In some cases, the method includes immersing the glass-based substrate in a second bath or a subsequent bath to produce a larger surface CS without significantly affecting the chemical depth and / or DOC of the layer. In such embodiments, the second bath or a subsequent bath may include a single metal (e.g., KNO3 or NaNO3) or a mixture of metals (KNO3 and NaNO3). The temperature of the second bath or a subsequent bath may be adjusted to produce a larger surface CS. In some embodiments, the immersion time of the glass-based substrate in the second bath or a subsequent bath may be adjusted to produce a larger surface CS without significantly affecting the chemical depth and / or DOC of the layer. For example, the immersion time in the second bath or a subsequent bath may be less than 10 hours (e.g., less than or equal to about 8 hours, less than or equal to about 5 hours, less than or equal to about 4 hours, less than or equal to about 2 hours, less than or equal to about 1 hour, less than or equal to about 30 minutes, less than or equal to about 15 minutes, or less than or equal to about 10 minutes).
[0213] In one or more alternative embodiments, the method may include one or more heat treatment steps, which may be used in conjunction with the ion exchange process described herein. Heat treatment includes heat treating the glass-based article to obtain a desired stress curve. In some embodiments, heat treatment includes annealing, tempering, or heating the glass-based substrate to a temperature of about 300-600° C. The heat treatment may last from 1 minute to up to about 18 hours. In some embodiments, heat treatment may be used after one or more ion exchange processes, or heat treatment may be used between ion exchange processes. Example
[0214] Various embodiments are further illustrated by the following examples. In the examples, before being strengthened, the examples are referred to as "substrates". After being strengthened, the examples are referred to as "articles" or "glass-based articles".
[0215] Example 1
[0216] A glass-ceramic substrate having the nominal composition shown in Table 2 below is provided. The glass-ceramic substrate has a thickness of 0.8 mm and includes a crystalline phase assembly comprising a β-spodumene solid solution as a primary crystalline phase and one or more secondary phases comprising rutile. The glass-ceramic substrate is immersed in a molten salt bath comprising NaNO3 at a temperature of 485°C for 10 hours (condition A), 13 hours (condition B) or 24 hours (condition C), or a molten salt bath comprising NaNO3 at 430°C for 2 hours (comparative condition D) to form a glass-ceramic article.
[0217] Table 2: Composition of the glass-ceramic substrate of Example 1 before chemical strengthening.
[0218]
[0219] The chemical distribution of the glass-ceramic article was measured by microprobe and is shown in Fig. 9 In formula (4), stress is proportional to concentration:
[0220] σ(z)=BE / 1-n(Cavg-C(z)) (4)
[0221] In formula (4), B is the lattice expansion coefficient, E is Young's modulus, n is Poisson's ratio, and Cavg is the concentration integral across samples. Fig. 9 As shown, when a higher temperature bath (i.e., Condition AC) is used, Na+ ions are exchanged through almost the entire thickness of the article. In this glass-ceramic, Na2O is present in the CT region in an amount of about 1.2 mol% or more. The glass-ceramic article ions exchanged in a lower temperature bath (Comparative Condition D) show a stress profile similar to the known stress profile.
[0222] Example 2
[0223] A glass substrate having the same composition and 0.8 mm thickness as shown in Table 2 but having an amorphous structure (and no crystalline phase) was chemically strengthened by immersing in a molten salt bath containing 100% NaNO3 at a temperature of about 430°C for different times to provide a glass article. The DOC and maximum CT values of the glass articles were measured using SCALP. Fig.10 As shown, the DOC and the maximum CT increase depend on the length of immersion or ion exchange. The maximum CT value is observed after the glass has been immersed for about 16 hours.
[0224] The stress distribution of the glass article of Example 2 was measured using SCALP and is shown in FIG. Fig.11 . The upper part of the y-axis representing the positive stress value is the CT layer and the lower part of the y-axis representing the negative stress value is the CS value. The stress distribution of the glass article that has been chemically strengthened for 16 hours shows a maximum CT value (i.e., 175 MPa) and a parabolic shape that substantially does not include a flat portion in the depth direction of 100 microns. The surface CS measured by SCALP is about 410 MPa. Therefore, the ratio of the absolute value of the maximum CT to the surface CS of Example 2 is about 0.4375. Fig.11 In the Figures, positive numbers are used for compressive stress, and negative numbers for tensile stress. These same conventions (compressive stress is represented as positive values on the y-axis, and tensile stress is represented as negative values on the y-axis) are also used in Figures 1-3 and 33. However, in the remaining figures, compressive stress is represented as negative values on the y-axis, and tensile stress is represented as positive values on the y-axis.
[0225] Example 3
[0226] For comparison, the glass-ceramic substrate of Example 1 and the glass substrate of Example 2, each having a thickness of about 0.8 mm, were chemically strengthened by immersion in a molten salt bath of NaNO 3 at a temperature of 350° C. for 3.5 hours (Examples 3A and 3B, respectively). Fig.12 The resulting stress distributions of the glass-ceramic articles and glass articles shown in (estimated by the chemical distribution measured by the microprobe using Equation 4) resemble an error function (erfc) or a quasi-linear shape. In addition, the CS depth of the layer is less than the depth of the alkali metal ions exchanged into the glass or glass-ceramic (or the chemical ion exchange depth).
[0227] When the glass-ceramic substrate of Example 1 and the glass substrate of Example 2, each having a thickness of about 0.8 mm, were subjected to chemical strengthening as described herein by immersion in a molten salt bath of NaNO at a temperature of 430° C. for 24 hours (Examples 3C and 3D, respectively), the resulting glass-based articles exhibited Fig.13 The metal oxide concentration profile shown in (obtained by EPMA). The metal oxide concentration profile is parabolic and shows ion exchange of Na+ ions throughout the entire thickness. The chemical distribution was measured using EMPA and the chemical depth of Na2O diffusion was shown to be equal to or greater than 400 microns. In addition, Na2O is present throughout the thickness, including in the CT layer, at a concentration of about 1 mol % or greater. The resulting glass-ceramic article of Example 3D shows excellent crack resistance in a drop test, wherein the glass-ceramic substrate is converted into the same mobile phone housing. Specifically, 5 samples of Example 3D were assembled into a mobile phone device and dropped onto sandpaper for continuous drops starting at a height of 50 cm. As each sample passed through a drop from a certain height, it fell again from an increasing height until it broke, and the height of failure of the sample at this point was recorded at Fig.13A Example 3D showed an average failure height of 172.5 cm.
[0228] Fig.14 The stress distribution of a glass-based substrate chemically strengthened according to a known method and a glass-based substrate chemically strengthened according to the method described herein is shown. Fig.14 As shown, the stress profile of the glass-based article of the embodiments described herein has a shape with substantially no flat portion (having a length or absolute depth greater than about 50 microns) and exhibits a DOC of about 0.2·t, while the known stress profile exhibits a substantially linear and / or flat portion starting from a depth of about 0.1 mm to about 0.7 mm (for a total length of about 0.6 mm or 600 microns). The known stress profile also exhibits a lower CT value and a lower DOC.
[0229] Example 4
[0230] Glass substrates having the composition of Table 2 (each having a thickness of about 1 mm) were chemically strengthened by immersion in a first molten salt bath of NaNO3 at a temperature of 430°C for 24 hours. One glass-based article did not undergo any other strengthening step (Example 4A). Three glass-based articles underwent a second strengthening step by immersion in a second molten salt bath of KNO3 at a temperature of about 430°C for 0.75 hours, 4 hours, or 8 hours (Examples 4B, 4C, and 4D, respectively). The stress distributions measured by SCALP of the resulting glass-based articles are shown in Fig.15 , the depth or thickness of the glass-based article is plotted on the x-axis and the stress is plotted on the y-axis. Positive stress values are CT values, while negative stress values are CS values. The spatial resolution of the equipment inhibits the measurement of the CS associated with the second KNO3 ion exchange step. The glass-based articles of Examples 4A and 4B show similar distributions. After immersion in the second strengthening step, the ratio-based articles of Examples 4C and 4D show a decreased CT (compared to Examples 4A and 4B) and an increased CS (compared to Examples 4A and 4B) over time. The glass-based articles of Examples 4C and 4D also show increased DOC compared to Examples 4A and 4B, and these DOC values are greater than 0.2·t.
[0231] Fig.16 The values of J / m for each of Examples 4B-4D are shown. 2 The stored tensile energy is greater than 15 J / m according to the time of immersion in the second molten salt bath of KNO3. 2 The stored tensile energy can be calculated from the measured SCALP stress distribution data and using the above formula (2).
[0232] Fig.17 and 18 The concentration profiles of K2O and Na2O, respectively, are shown as a function of depth (in micrometers) for each of Examples 4B-4D. Fig.17 As shown, the chemical depth of K2O is 3 microns (Example 4B, immersed in a KNO3 bath for 0.75 hours), 6 microns (Example 4C, immersed in a KNO3 bath for 4 hours) and 5 microns (Example 4D, immersed in a KNO3 bath for 8 hours). Fig.18 As shown, Na2O penetrated the entire depth and had a concentration of about 1 mol% or greater along the entire depth of the glass-based article for each of Examples 4B-4D.
[0233] Examples 4E and 4F include glass substrates having the composition of Table 2 (each having a thickness of about 1 mm), which were chemically strengthened by immersion in a first molten salt bath of NaNO3 at a temperature of 430°C for 24 hours, followed by heat treatment in air to a temperature of 430°C for 4 hours or 8.25 hours, respectively. Fig.19 The glass-based stress distributions of Examples 4E and 4F are shown in FIG. , and the stress distributions of Examples 4A, 4C and 4D are shown for comparison. Fig. 20 At a smaller scale, it is shown Fig.19 The same images are shown in Figure 2 to show the difference in stress distribution at or near a depth of 0.5·t.
[0234] Example 5
[0235] Glass substrates having the composition of Table 2 (each having a thickness of about 1 mm) were chemically strengthened by immersion in a first molten salt bath of NaNO3 at a temperature of 430°C for 24 hours. One glass-based article did not undergo any other strengthening step (Example 5A). Two glass-based articles were subjected to a second strengthening step by placing the glass-based article in a furnace at 390°C and keeping the glass-based article in the furnace for about 8 hours or 28 hours (Examples 5B-5C, respectively). Four glass-based articles were subjected to a third strengthening step (after the first strengthening step and any different second strengthening step) by immersion in a second molten salt bath of KNO3 at a temperature of 430°C for 4 hours or 8 hours. The strengthening steps for each of Examples 5A-5G are shown in Table 3. The measured CT values are also shown in Table 3.
[0236] Table 3: Intensification steps for Examples 5A-5G.
[0237]
[0238]
[0239] The stress distribution of the obtained glass-based product is shown in Fig.21 , the depth or thickness of the glass-based article is plotted on the x-axis and the stress is plotted on the y-axis. Positive stress values are CT values, while negative stress values are CS values. Fig.21 As shown in FIG. 1 , as the duration of the second and / or third heat treatment increases, DOC increases and CT decreases. The decreases in DOC and CT are respectively Fig. 22 and 23 More clearly shown in.
[0240] The glass-based articles of Examples 5A-5G were then subjected to a poke test, in which one side of the glass-based article was taped to an adhesive tape and the opposite bare side was struck and broken with a sharp tool. The number of pieces of fragments obtained can be correlated to the stored tensile energy of the glass-based article. Examples 5A, 5B, and 5D showed many fragments (i.e., more than 50 and even 100 pieces), while Example 5F showed 10 fragments, Example 5C showed 3 fragments, and Examples 5E and 5G showed 4 fragments. Examples 5A, 5B, and 5D, which broke into many fragments (more than about 100 MPa), showed higher CT than Examples 5C, 5E, 5F, and 5G (all of which had CT values of about 100 MPa or less).
[0241] Example 6
[0242] Glass substrates having the nominal compositions shown in Table 2 and each having a thickness of about 1 mm were subjected to chemical strengthening in a molten salt bath having a temperature of 430° C. and containing NaNO 3. The duration of immersion of the glass substrates in the molten salt bath is shown in Table 5.
[0243] Table 4: Chemical strengthening duration (or ion exchange time) for Examples 6A-6G.
[0244]
[0245]
[0246] The stress distribution of the glass-based articles of Examples 6A-6G is as follows: Fig.24 As shown. The stress distribution is measured using SCALP. Fig.24 As shown, immersion of the glass substrate in the molten salt bath for 16 hours and 24 hours produces a glass-based article showing the maximum CS value and the maximum CT value in absolute terms. A graph showing the change in CT value and stored tensile energy with ion exchange time is shown in Fig.25 .
[0247] Example 7
[0248] Glass substrates having a nominal composition as shown in Table 2 and a thickness of about 0.8 mm were subjected to chemical strengthening in a molten salt bath containing a mixture of NaNO3 and NaSO4 and a temperature of 500°C for 15 minutes (Comparative Example 7A) and 16 hours (Example 7B). The stress distributions of the glass-based articles of Examples 7A and 7B are shown in Table 2. Fig.26 As shown. Fig.26As shown, Comparative Example 7A exhibits a known stress profile, while Example 7B exhibits a stress profile according to one or more embodiments herein. The stored tensile energy of the glass-based articles of Examples 7A and 7B was calculated in the same manner as Examples 4B-4D. The calculated stored tensile energy was plotted as a function of the measured CT (MPa), as shown in FIG. Fig. 27 shown.
[0249] like Fig. 27 As shown in Figure 1, for a given CT value, Comparative Example 7A exhibits much greater stored tensile energy than Example 7B (same CT value). In this figure, CT is the maximum CT in the sample. Specifically, at a CT of about 55 MPa, Comparative Example 7A exhibits about 12.5 J / m 2 The stored tensile energy of Example 7B is about 9 J / m 2 The stored tensile energy of Comparative Example 7A and Example 7B broke, and the number of pieces broken by Example 7B was less than that of Comparative Example 7A (which broke into significantly more pieces). Therefore, without wishing to be bound by theory, it is believed that controlling the stored tensile energy can provide a way to control or predict the fracture pattern or the number of pieces of fragments produced by fracture. In these examples, CT was changed by keeping the sample in the ion exchange bath for a longer time while using the same bath temperature and composition. Fig. 27 The point 0,0 is not experimentally obtained, but is what a technician in this field would expect, that is, when 0CT, there will be 0 stored tensile energy.
[0250] Glass substrates having a nominal composition as shown in Table 2 and a thickness of about 1 mm were subjected to chemical strengthening in a molten salt bath containing NaNO3 and a temperature of 430°C for 4 hours (Comparative Example 7C) and 61.5 hours (Example 7D). Comparative Example 7C exhibits a known stress profile, while Example 7D exhibits a stress profile according to one or more embodiments of the present invention. The stored tensile energy of Examples 7C and 7D was calculated using the same method used for Examples 4B-4D and plotted as a function of the measured CT (MPa), as shown in FIG. Fig.28 shown.
[0251] like Fig.28 As shown, for a given CT, Comparative Example 7C exhibits a much higher stored tensile energy value than Example 7D (same CT value) (same, as Fig. 27 As shown, these are the maximum CT values, and again, the values are changed by using the same ion exchange bath temperature and composition, but for a longer time). Comparative Example 7C and Example 7D broke, and Example 7D broke into fewer pieces than Comparative Example 7C (which broke into significantly more pieces).
[0252] Example 8
[0253] A glass substrate having a nominal composition of 70.9 mol % SiO2, 12.8 mol % Al2O3, 1.95 mol % B2O3, 7.95 mol % Li2O, 2.43 mol % Na2O, 2.98 mol % MgO, 0.89 mol % ZnO, and 0.1 mol % SnO2 and a thickness of about 0.8 mm was subjected to the ion exchange conditions of Table 5. Various properties of Example 8 are compared with Example 2 in Table 6.
[0254] Table 5: Ion exchange conditions for Example 8.
[0255]
[0256] Table 6: Comparison of properties of Example 8 and Example 2.
[0257]
[0258]
[0259] The stress profile of the glass-based article of Example 8 was measured and exhibited the shape described herein.
[0260] Glass substrates of Example 2, Comparative Examples 8A and 8B having the same thickness as Example 8 were provided. The glass substrate of Example 2 was ion exchanged in a molten bath of 100% NaNO3 at a temperature of 430°C for 33 hours. Comparative Example 8A was ion exchanged in a molten bath of 100% NaNO3 at a temperature of 390°C for 16 hours and also exhibited a known error function stress profile. The glass substrate of Example 8B included a nominal composition of 57.5 mol% SiO2, 16.5 mol% Al2O3, 16.7 mol% Na2O, 2.5 mol% MgO, and 6.5 mol% P2O5 and was ion exchanged to exhibit a known error function stress profile. The term "error function stress profile" as used herein refers to a stress profile similar to that of FIG. 1.
[0261] The glass-based articles of Example 2, Example 8, and Comparative Examples 8A and 8B are then retrofitted onto the same mobile phone device. The phone device is dropped onto 30-grit sandpaper from increasing heights starting from 20 cm. If the glass-based article withstands the drop starting from a height (e.g., 20 cm), the mobile phone is dropped again from a higher height (e.g., 30 cm, 40 cm, 50 cm, etc.). The height at which the glass-based article was damaged is plotted in FIG. 29, which also shows the average damage height of the samples of Examples 2, and 8, and Comparative Examples 8A and 8B. As shown in FIG. 29, Examples 2 and 8 show damage at a drop height that is significantly higher than Comparative Examples 8A and 8B. Specifically, Comparative Examples 8A and 8B show damage at drop heights of approximately 38 cm and 55 cm, respectively, while Examples 2 and 8 show damage at drop heights of approximately 147 cm and 132 cm, respectively.
[0262] The same test was repeated with a new sample on 180 grit sandpaper using the same mobile phone device. The average failure height of Comparative Example 8A was 204 cm, the average failure height of Comparative Example 8B was 190 cm, and the average failure height of Example 2 was 214 cm and the average failure height of Example 8 was 214 cm.
[0263] The glass substrate of Comparative Example 8C having a nominal composition of 65 mol% SiO2, 5 mol% B2O3, 14 mol% Al2O3, 14 mol% Na2O, 2 mol% MgO, and 0.1 mol% SnO2 and a thickness of 0.8 mm was ion exchanged to exhibit a known error function stress profile. Examples 2 and Comparative Example 8B (in which the above stress profiles were exhibited), the glass-based article samples of Comparative Example 8C, and the glass-based article of Example 8 (ion exchanged under Condition 5), as shown in Table 5, were subjected to the A-ROR test described herein.
[0264] Examples 6 and 8 and Comparative Example 8C were polished using loads or pressures of 25 psi and 45 psi, and Example 2 was polished using only a load of 25 psi. Fig.30 As shown. Fig.30 As shown, Examples 2 and 8 show higher breaking loads than Comparative Example 8B and Comparative Example 8C at corresponding grinding loads or pressures.
[0265] The glass-based article samples of Example 2 (after ion exchange as described above in this example) and 8 (after ion exchange according to Condition 4) were subjected to a 4-point bending test. The results are shown in Fig.31 Weibull distribution plot of . Fig.31 As shown, Example 8 exhibits a higher failure load or stress (eg, greater than about 400 MPa).
[0266] As shown above, glass-based articles made from compositions having strain points exceeding 525° C. enable ion exchange temperatures (or ion exchange bath temperatures) to be in the range of about 350° C. to about 480° C. In some embodiments, glass compositions that exhibit monovalent ion diffusion exceeding about 800 square microns per hour enable metal oxides diffused into the glass-based article to quickly penetrate the entire depth or thickness of the article to minimize stress relaxation. Excessive stress relaxation can reduce the surface compressive stress of the glass-based article.
[0267] It will be apparent to those skilled in the art that various modifications and variations can be made in the present invention without departing from the scope or spirit of the inventions.
[0268] Example 9
[0269] A glass substrate having the same composition as Example 8 and a thickness of about 0.8 mm was subjected to ion exchange by immersion in a 100% NaNO 3 molten salt bath at a temperature of 430° C. according to the conditions provided in Table 7. The resulting glass-based article exhibited a maximum CT value of Fig.32 The ions were plotted as a function of the ion exchange time.
[0270] Table 7: Ion exchange conditions for Examples 9A-9E.
[0271] Example Time in bath (hours) Maximum CT(MPa) 9A 2 hours 105 9B 4 hours 145 9C 8 hours 144 9D 16.5 hours 115 9E 24 hours 79
[0272] The stress profile of Example 9D was measured using refractive near field (RNF) measurements as described in U.S. Patent No. 8,854,623, entitled “Systems and methods for measuring a profile characteristic of a glass sample,” which is incorporated herein by reference in its entirety. Fig.33 The measured stress is shown as a function of the depth extending from the surface of the glass-based article into the glass-based article of Example 9D. Shown in Table 8 are the stresses at specific depths, including the stress at the "knee point" where the slope of the stress changes dramatically.
[0273] Table 8: Stress at specific depths for Example 9D.
[0274] Depth (micrometers) Stress(MPa) 12 ("turning point") 151 50 105 100 66 150 20
[0275] Example 10
[0276] Example 10A includes a glass substrate having the same composition as Example 1 and having a thickness of 0.8 mm. The glass substrate is ion exchanged in a single molten salt bath containing 80% KNO3 and 20% NaNO3 at a temperature of about 430°C for 16 hours. The resulting glass-based article exhibits a stress distribution as shown in Table 9.
[0277] Table 9: Stress distribution of Example 10A.
[0278]
[0279] The glass-based articles according to Example 10A were subjected to AROR testing as described herein. One group of glass-based articles was ground with a 5 psi pressure or load, a second group of glass-based articles was ground with a 25 psi pressure or load, and a third group of glass-based articles was ground with a 45 psi pressure or load. The AROR data are shown in Table 1. Fig.34 As shown. Fig.34 As shown, all glass-based articles according to Example 10A exhibited an average failure load greater than about 25 kgf.
[0280] The glass-based article according to Example 10A is retrofitted on the same mobile phone device. The phone device is dropped onto 180 grit sandpaper from increasing heights starting at 20 cm. If the glass-based article survives the drop starting from one height (e.g., 20 cm), the mobile phone is dropped again from higher heights (e.g., 30 cm, 40 cm, 50 cm, etc.) until the height is 225 cm. The glass-based article that passed the test is then dropped onto 30 grit sandpaper (same phone device). The heights at which the glass-based article failed the test on 180 grit sandpaper and 30 grit sandpaper are plotted on the graph. Fig.35 In. Fig.35 As shown, all but three of the glass-based articles of Example 10A passed the drop onto 180 grit sandpaper at a height of up to about 225 cm (yielding an average passing drop height of about 215 cm). The average passing drop height onto 30 grit sandpaper was 132 cm.
[0281] The glass-based article according to Example 10A exhibits a dielectric constant of about 5.8 to about 6 in a frequency range of about 480 mHz to about 3000 mHz. The glass-based article according to Example 10A exhibits a dielectric loss tangent of about 0.010 to about 0.013 in a frequency range of about 480 mHz to about 3000 mHz.
[0282] The glass-based article according to Example 10A has a refractive index of about 1.496 to about 1.523 at about 380 nm to about 1550 nm, and a refractive index of about 1.496 to about 1.503 at about 380 nm to about 800 nm.
[0283] The glass-based articles according to Example 10A were subjected to various chemical treatments as shown in Table 10. The chemical durability of the glass-based articles was compared with Comparative Examples 10B, 10C, and 10D. Comparative Example 10B was a glass substrate having a nominal composition of 64.3 mol% SiO2, 7.02 mol% B2O3, 14 mol% Al2O3, 14 mol% Na2O, 0.5 mol% K2O, 0.03 mol% Fe2O3, and 0.1 mol% SnO2. Comparative Example 10C was a glass substrate having a nominal composition of 64.75 mol% SiO2, 5 mol% B2O3, 14 mol% Al2O3, 13.75 mol% Na2O, 2.4 mol% MgO, and 0.08 mol% SnO2. Comparative Example 10D was a glass substrate having the following nominal composition: 57.5 mol % SiO2, 16.5 mol % Al2O3, 16.71 mol % Na2O, 2.8 mol % MgO, 0.05 mol % SnO2, and 6.5 mol % P2O5.
[0284] Table 10: Chemical durability of Example 10A and Comparative Examples 10B, 10C and 10D.
[0285]
[0286]
[0287] Embodiment 11
[0288] Example 11A included a glass substrate having the same composition as Example 1 and having a thickness of 0.8 mm. Comparative Example 11B included a glass substrate having the same composition as Comparative Example 10D and having a thickness of 0.8 mm. The glass substrate of Example 11A was chemically strengthened in a single step using a single bath, as described in Table 11. The glass substrate of Comparative Example 3B was ion exchanged in a two-step process, as described in Table 11.
[0289] Table 11: Ion exchange conditions of Example 11A and Comparative Example 11B
[0290]
[0291]
[0292] The glass-based articles according to Example 11A and Comparative Example 11B were retrofitted on the same mobile phone device. The phone device was dropped onto 30-grit sandpaper from increasing heights starting at 20 cm. The heights at which the glass-based articles failed the test on the 30-grit sandpaper were plotted on the graph. Fig.36 In. Fig.36As shown, the glass-based article of Example 11A exhibited an average drop height through testing (ie, 127 cm) that was more than three times the average drop height through testing of Comparative Example 11B (ie, 38 cm).
[0293] The glass-based articles according to Example 11A and Comparative Example 11B were subjected to AROR testing, using a load or pressure of 25 psi, as described herein. The glass-based substrate of Example 10A exhibited an average failure load of about 31.3 kgf, while the glass-based substrate of Comparative Example 10B exhibited an average failure load of about 27.4 kgf, as described herein. Fig.37 As shown. When the grinding load or pressure increases to 45 psi, the difference in average breaking load between Example 10A and Comparative Example 10B increases. Specifically, under a load or pressure of 45 psi, Example 10A exhibits an average breaking load of about 28.9 kgf, while Comparative Example 10B exhibits an average breaking load of about 19.6 kgf, as shown. Fig.38 shown.
[0294] Example 12
[0295] Examples 12A and 12B include glass substrates having the nominal composition of Example 1H and a thickness of 0.8 mm. The glass substrate of Example 12A was chemically strengthened in a bath having 6.5% Na:93.5% K at 430° C. for 4.5 hours and produced a CS of about 656, a DOL of about 8.1, and a CS of about 105 to about 130 MPa. k (or compressive stress at the inflection point). The substrate of Example 12B was chemically strengthened in a bath having 7% Na:93% K at a temperature of 430°C for 4.5 hours and resulted in a CS of about 640 MPa, a DOL of about 8.2, and a CS of about 100 MPa. k Inverted Ball on Sandpaper (IBoS) testing was performed on Examples 12A and 12B according to the procedure described herein. Testing was performed using 30 grit sandpaper and a 4.2 g stainless steel ball having a diameter of 10 mm.
[0296] Table 12: Sample thickness, depth of layer (DOL), surface compressive stress (CS), estimated average rupture height, and percentage passing (surv.) at various heights for samples tested by IBoS.
[0297]
[0298] Sample group 12A showed an average rupture height of 88 cm. In addition, 4 of the 5 samples withstood drop heights of 75 cm, 80 cm, 85 cm, 90 cm, and 95 cm, respectively, yielding 80% survival rates at each of these heights. Sample group 12B showed an average rupture height of 76 cm. In addition, 3 of the 5 samples withstood drop heights of 75 cm, 80 cm, and 85 cm, respectively, yielding 60% survival rates at each of these heights.
[0299] Sample groups 12A and 12B were also subjected to the Knoop scratch threshold test described above. The samples of group 12A had a Knoop scratch threshold of more than 7N and less than 14N. In other aspects, the samples of group 12B had a Knoop scratch threshold of more than 10N and less than 16N.
[0300] It is obvious to those skilled in the art that various modifications and variations can be made to the present invention without departing from the scope or spirit of the present invention. For example, various features can be combined according to the following exemplary embodiments.
[0301] Embodiment 1, a glass-based product, comprising:
[0302] a first surface defining an area (square inches) and a second surface, the second surface being opposite the first surface, and both defining a thickness (t);
[0303] a concentration of the metal oxide that is non-zero and varies along a thickness range from about 0·t to about 0.3·t; and
[0304] The CT region includes the maximum central tension (CT) of 71.5 / √(t) to 100 / √(t),
[0305] Wherein, when the glass-based article breaks, the glass-based article breaks into more than 2 pieces / inch 2 A glass-based article wherein the sample size is a 5.08 cm x 5.08 cm (2 inch x 2 inch) square.
[0306] Embodiment 2, the glass-based article of embodiment 1, wherein the concentration of the metal oxide is non-zero and varies throughout the thickness.
[0307] Embodiment 3, the glass-based article as described in embodiment 1 or 2, wherein the monovalent ions of the metal oxide generate stress along the thickness range.
[0308] Embodiment 4, a glass-based article as described in any of the preceding embodiments, wherein the concentration of the metal oxide decreases from the first surface to a value at a point between the first surface and the second surface, and increases from this value to the second surface.
[0309] Embodiment 5, the glass-based article as described in any of the preceding embodiments, further comprises a surface compressive stress (CS) greater than or equal to about 300 MPa.
[0310] Embodiment 6, a glass-based article as described in embodiment 5, wherein the surface CS is greater than or equal to about 400 MPa.
[0311] Embodiment 7. A glass-based article as described in any of the preceding embodiments, wherein the concentration of the metal oxide is greater than or equal to about 0.05 mol % throughout the thickness.
[0312] Embodiment 8. The glass-based article of any of the preceding embodiments, wherein the concentration of the metal oxide at the first surface is about 1.5 times the concentration of the metal oxide at a depth equal to about 0.5·t.
[0313] Embodiment 9, a glass-based article as described in any of the preceding embodiments, wherein the glass-based article comprises the metal oxide in a total concentration of about 1 mol % to about 15 mol %.
[0314] Embodiment 10, a glass-based article as described in any of the preceding embodiments, wherein the metal oxide comprises any one or more of the following: Li2O, Na2O, K2O, Rb2O, and Cs2O.
[0315] Embodiment 11, a glass-based article as described in any of the preceding embodiments, further comprising a surface CS greater than or equal to about 200 MPa, and a chemical layer depth greater than or equal to about 0.4t.
[0316] Embodiment 12, the glass-based article of any of the preceding embodiments, further comprising a CS layer extending from the first surface to the DOC, wherein the DOC is greater than or equal to about 0.1·t.
[0317] Embodiment 13, a glass-based article as described in any of the preceding embodiments, wherein the CT region comprises a metal oxide.
[0318] Embodiment 14. The glass-based article of embodiment 11, wherein the ratio of the maximum CT to the absolute value of the surface CS is from about 0.1 to about 0.8.
[0319] Embodiment 15, a glass-based article as described in any of the preceding embodiments, wherein t comprises less than or equal to about 3 mm.
[0320] Embodiment 16, the glass-based article as described in any of the preceding embodiments, further comprises an amorphous structure.
[0321] Embodiment 17, the glass-based article as described in embodiments 1-15, also includes a crystal structure.
[0322] Embodiment 18, the glass-based article as described in any of the preceding embodiments, exhibits a light transmittance greater than or equal to about 88% in the wavelength range of about 380 nm to about 780 nm.
[0323] Embodiment 19, a glass-based article as described in any of the preceding embodiments, further exhibits the following CIELAB color space coordinates under CIE illuminant F02 conditions: L* value greater than or equal to about 88, a* value from about -3 to about +3, and b* value from about -6 to about +6.
[0324] Embodiment 20, the glass-based article as described in any of the preceding embodiments, further comprising:
[0325] a first metal oxide concentration and a second metal oxide concentration,
[0326] wherein, over a first thickness range of about 0·t to about 0.5·t, the first metal oxide concentration ranges from about 0 mol % to about 15 mol %, and
[0327] Wherein, within a second thickness range of about 0 micrometers to about 25 micrometers, the concentration of the second metal oxide is in a range of about 0 mol % to about 10 mol %.
[0328] Embodiment 21, the glass-based article as described in embodiment 20, further comprising a third metal oxide.
[0329] Embodiment 22, a glass-based article as described in any of the preceding embodiments, further comprising a Young's modulus greater than or equal to about 70 GPa.
[0330] Embodiment 23, the glass-based article of any of the preceding embodiments, further comprising a liquidus viscosity of less than about 100 kilopoise (kP).
[0331] Embodiment 24, the glass-based article as described in any of the preceding embodiments, further comprising any one or more of the following:
[0332] A composition comprising about 17 mol % or less of the total amount of Al2O3 and Na2O,
[0333] A composition comprising about 4 mol % or less Na2O,
[0334] A composition comprising any one or more of B2O3 and ZnO, and
[0335] There is basically no P2O5 composition.
[0336] Embodiment 25, a device comprising:
[0337] a housing having a front surface, a rear surface, and side surfaces;
[0338] an electronic assembly at least partially located within the housing;
[0339] a display located on or adjacent to the front surface of the housing; and
[0340] A cover substrate disposed on a display, wherein the cover substrate comprises the glass-based article of any one of embodiments 1-24.
[0341] Embodiment 26, a glass-based article comprising:
[0342] A first surface and a second surface opposite the first surface, both defining a thickness (t) equal to or less than about 3 millimeters; and
[0343] The stress distribution along the thickness,
[0344] wherein all points of the stress distribution within the thickness range of about 0·t up to 0.3·t and greater than 0.7t include a tangent line having an absolute value of a slope greater than about 0.1 MPa / micrometer,
[0345] wherein the stress profile comprises a maximum CS, a DOC, and a maximum CT ranging from about 71.5 / √(t) to about 100 / √(t), wherein a ratio of an absolute value of the maximum CT to the maximum CS is from about 0.01 to about 0.2, and wherein the DOC is greater than or equal to about 0.1·t, and
[0346] Wherein, when the glass-based article breaks, the glass-based article breaks into at least 2 pieces / inch 2 , where the sample size is a square of 5.08 cm×5.08 cm (2 inches×2 inches).
[0347] Embodiment 27, a glass-based article as described in Embodiment 26, further comprising a surface CS greater than or equal to about 300 MPa.
[0348] Embodiment 28, a glass-based article as described in embodiment 26 or 27, further comprising a surface CS greater than or equal to about 200 MPa, and a chemical layer depth greater than or equal to about 0.4·t.
[0349] Embodiment 29, a glass-based article as described in any of Embodiments 26-28, further comprising a CS layer extending from the first surface to the DOC, wherein the DOC is greater than or equal to about 0.1·t.
[0350] Embodiment 30, a glass-based article as described in any of embodiments 26-29, further comprising a CT region, wherein the CT region comprises a non-zero and varying metal oxide concentration.
[0351] Embodiment 31, a glass-based article as described in any of embodiments 26-30, further comprising a ratio of the absolute value of the maximum CT to the surface CS of about 0.1 to about 0.8.
[0352] Embodiment 32, a glass-based article as described in any of embodiments 26-31, further comprising a Young's modulus greater than or equal to about 70 GPa.
[0353] Embodiment 33, a glass-based article as described in any of embodiments 26-32, further comprising a liquidus viscosity of less than about 100 kP.
[0354] Embodiment 34, the glass-based article of any one of embodiments 26-33, further comprising any one or more of the following:
[0355] A composition comprising about 17 mol % or less of the total amount of Al2O3 and Na2O,
[0356] A composition comprising about 4 mol % or less Na2O,
[0357] A composition comprising any one or more of B2O3 and ZnO, and
[0358] There is basically no P2O5 composition.
[0359] Embodiment 35, a device comprising:
[0360] a housing having a front surface, a rear surface, and side surfaces;
[0361] an electronic assembly at least partially located within the housing;
[0362] a display located on or adjacent to the front surface of the housing; and
[0363] A cover substrate disposed on a display, wherein the cover substrate comprises the glass-based article of any one of embodiments 26-34.
[0364] Embodiment 36, a glass-based article comprising:
[0365] a first surface and a second surface opposite the first surface, both defining a thickness (t); and
[0366] a concentration of the metal oxide that is non-zero and varies along a thickness range from about 0·t to about 0.3·t;
[0367] a surface compressive stress greater than or equal to about 200 MPa; and
[0368] A CT region having a maximum CT of about 71.5 / √(t) to about 100 / √(t).
[0369] Embodiment 37, a glass-based article as described in embodiment 36, wherein the thickness range of the metal oxide concentration is about 0·t to about 0.4·t.
[0370] Embodiment 38, a glass-based article as described in embodiment 36 or 37, wherein the thickness range of the metal oxide concentration is about 0·t to about 0.45·t.
[0371] Embodiment 39, a glass-based article as described in any of embodiments 36-38, wherein the monovalent ions of the metal oxide produce stress along the thickness range.
[0372] Embodiment 40, a glass-based article as described in embodiment 39, wherein the monovalent ion of the metal oxide has the largest ion diameter among all monovalent ions of the metal oxide in the glass-based substrate.
[0373] Embodiment 41, a glass-based article as described in any of embodiments 36-40, wherein the concentration of the metal oxide decreases from the first surface to a value at a point located between the first surface and the second surface, and increases from this value to the second surface.
[0374] Embodiment 42. The glass-based article of any one of embodiments 36-41, wherein when the glass-based article breaks, the glass-based article breaks into at least 1 fragment / inch. 2 Up to 40 pieces / inch 2 , where the sample size is a 5.08 cm x 5.08 cm (2 in x 2 in) square.
[0375] Embodiment 43. The glass-based article of any one of embodiments 36-42, wherein the glass-based article comprises a thickness of about 450 μm or greater at about 460° C. 2 / hour sodium or potassium ion diffusion coefficient, and a DOC greater than about 0.15·t, and wherein the surface CS is 1.5 times or greater than the maximum CT.
[0376] Embodiment 44. The glass-based article of any one of embodiments 36-43, wherein the glass-based article comprises a relative humidity greater than or equal to about 0.65 MPa·m 1 / 2 The fracture toughness (K 1C ).
[0377] Embodiment 45, a glass-based article as described in any of embodiments 36-44, wherein the surface CS is greater than the maximum CT.
[0378] Embodiment 46, a glass-based article as described in any of embodiments 36-45, wherein the surface CS is greater than or equal to about 300 MPa and the thickness is less than or equal to about 2 mm.
[0379] Embodiment 47, a glass-based article as described in any of Embodiments 36-46, wherein the concentration of the metal oxide is greater than or equal to about 0.05 mol% throughout the thickness.
[0380] Embodiment 48, a glass-based article as described in any of embodiments 36-47, wherein the concentration of the metal oxide at the first surface is about 1.5 times the concentration of the metal oxide at a depth equal to about 0.5·t.
[0381] Embodiment 49, a glass-based article as described in any of embodiments 36-48, wherein the total concentration of the metal oxides is from about 1 mol% to about 15 mol%.
[0382] Embodiment 50, a glass-based article as described in any of embodiments 36-49, further comprising a chemical layer depth greater than or equal to about 0.4·t.
[0383] Embodiment 51, a glass-based article as described in any of embodiments 36-50, further comprising a CS layer extending from the first surface to the DOC, wherein the DOC is greater than or equal to about 0.1·t.
[0384] Embodiment 52, a glass-based article as described in any of embodiments 36-51, wherein the CT region comprises a metal oxide.
[0385] Embodiment 53, a glass-based article as described in any of embodiments 36-52, wherein the ratio of the maximum CT to the absolute value of the surface CS is about 0.1 to about 0.8.
[0386] Embodiment 54, a glass-based article as described in any of embodiments 36-53, wherein t comprises less than or equal to about 3 mm.
[0387] Embodiment 55, a glass-based article as described in any of embodiments 36-54, further comprising a Young's modulus greater than or equal to about 70 GPa.
[0388] Embodiment 56, a glass-based article as described in any of embodiments 36-55, further comprising a liquidus viscosity of less than about 100 kP.
[0389] Embodiment 57, the glass-based article of any one of embodiments 36-56, further comprising any one or more of the following:
[0390] A composition comprising about 17 mol % or less of the total amount of Al2O3 and Na2O,
[0391] A composition comprising about 4 mol % or less Na2O,
[0392] A composition comprising any one or more of B2O3 and ZnO, and
[0393] There is basically no P2O5 composition.
[0394] Embodiment 58, a device comprising:
[0395] a housing having a front surface, a rear surface, and side surfaces;
[0396] an electronic assembly at least partially located within the housing;
[0397] a display located on or adjacent to the front surface of the housing; and
[0398] A cover substrate disposed on a display, wherein the cover substrate comprises the glass-based article of any one of embodiments 36-57.
[0399] Embodiment 59, a glass-based article comprising:
[0400] a first surface and a second surface opposite the first surface, both defining a thickness (t); and
[0401] Forming a concentration gradient of metal oxides,
[0402] wherein the concentration of the metal oxide decreases from the first surface to a value located at a point between the first surface and the second surface and increases from this value to the second surface,
[0403] wherein the concentration of the metal oxide at this point is not zero, and
[0404] Wherein, the glass-based product comprises about greater than 0J / m 2 To less than 20J / m 2 of stored tensile energy, and a Young's modulus greater than or equal to about 70 GPa.
[0405] Embodiment 60, a glass-based article as described in embodiment 59, further comprising a surface CS greater than or equal to about 300 MPa.
[0406] Embodiment 61, a glass-based article as described in embodiment 59 or 60, wherein the concentration of the metal oxide is greater than or equal to about 0.05 mol% throughout the thickness range.
[0407] Embodiment 62, a glass-based article as described in any of embodiments 59-61, wherein the concentration of the metal oxide at the first surface is about 1.5 times the concentration of the metal oxide at a depth equal to about 0.5t.
[0408] Embodiment 63, a glass-based article as described in any of embodiments 59-62, wherein the total concentration of the metal oxides is from about 1 mol % to about 15 mol %.
[0409] Embodiment 64, a glass-based article as described in any of embodiments 59-63, wherein the metal oxide includes any one or more of the following: Li2O, Na2O, K2O, Rb2O and Cs2O.
[0410] Embodiment 65, a glass-based article as described in any of embodiments 59-64, further comprising a CS layer extending from the first surface to the DOC, wherein the DOC is greater than or equal to about 0.1·t.
[0411] Embodiment 66, a glass-based article as described in any of embodiments 59-65, also includes a CT region, wherein the CT region includes a metal oxide concentration gradient.
[0412] Embodiment 67, a glass-based article as described in embodiment 66, wherein the CT region includes a maximum CT and a ratio of the absolute value of the maximum CT to the surface CS is about 0.1 to about 0.8.
[0413] Embodiment 68, a glass-based article as described in any of embodiments 59-67, wherein t comprises less than or equal to about 3 mm.
[0414] Embodiment 69, a glass-based article as described in embodiment 67, wherein the range of the maximum CT is about 71.5 / √(t) to about 100 / √(t).
[0415] Embodiment 70, a glass-based article as described in any of embodiments 59-69, further comprising a liquidus viscosity of less than about 100 kP.
[0416] Embodiment 71, the glass-based article of any one of embodiments 59-70, further comprising any one or more of the following:
[0417] A composition comprising about 17 mol % or less of the total amount of Al2O3 and Na2O,
[0418] A composition comprising about 4 mol % or less Na2O,
[0419] A composition comprising any one or more of B2O3 and ZnO, and
[0420] There is basically no P2O5 composition.
[0421] Embodiment 72, a device comprising:
[0422] a housing having a front surface, a rear surface, and side surfaces;
[0423] an electronic assembly at least partially located within the housing;
[0424] a display located on or adjacent to the front surface of the housing; and
[0425] A covering substrate disposed on a display, wherein the covering substrate comprises the glass-based article of any one of embodiments 59-71.
[0426] Embodiment 73, a glass-based article comprising:
[0427] A first surface and a second surface opposite the first surface, both defining a thickness (t) equal to or less than about 3 millimeters; and
[0428] The stress distribution along the thickness,
[0429] wherein the stress distribution at all points between the thickness range from about 0·t up to 0.3·t and exceeding 0.7·t comprises a tangent line having an absolute value of a slope greater than about 0.1 MPa / micrometer,
[0430] wherein the stress profile comprises a maximum CS, a DOC and a maximum CT, wherein a ratio of an absolute value of the maximum CT to the maximum CS is from about 0.01 to about 0.2, and wherein the DOC is greater than or equal to about 0.1·t, and
[0431] Wherein, the glass-based product comprises about greater than 0J / m 2 To less than 20J / m 2 of stored tensile energy, and a Young's modulus greater than or equal to about 70 GPa.
[0432] Embodiment 74, a glass-based article as described in embodiment 73, also includes a non-zero concentration of metal oxide that varies continuously along the entire thickness.
[0433] Embodiment 75, the glass-based article of embodiment 73 or 74, further comprising a non-zero concentration of the metal oxide that varies continuously along a thickness segment of less than about 10 microns.
[0434] Embodiment 76, a glass-based article as described in any of embodiments 73-75, wherein the maximum CS comprises greater than or equal to about 300 MPa.
[0435] Embodiment 77, a glass-based article as described in any of embodiments 73-76, also includes a chemical layer depth greater than or equal to about 0.4·t.
[0436] Embodiment 78, as a glass-based article as described in any of embodiments 73-77, also includes a CT region, wherein the CT region includes a metal oxide concentration gradient.
[0437] Embodiment 79, a glass-based article as described in any of embodiments 73-78, wherein t comprises less than or equal to about 3 mm.
[0438] Embodiment 80, a glass-based article as described in any of embodiments 73-79, wherein the maximum CT is greater than or equal to 71.5 / √(t).
[0439] Embodiment 81, a glass-based article as described in any of embodiments 73-80, further comprising a liquidus viscosity of less than about 100 kP.
[0440] Embodiment 82, the glass-based article of any one of embodiments 73-81, further comprising any one or more of the following:
[0441] A composition comprising about 17 mol % or less of the total amount of Al2O3 and Na2O,
[0442] A composition comprising about 4 mol % or less Na2O,
[0443] A composition comprising any one or more of B2O3 and ZnO, and
[0444] There is basically no P2O5 composition.
[0445] Embodiment 83, a device comprising:
[0446] a housing having a front surface, a rear surface, and side surfaces;
[0447] an electronic assembly at least partially located within the housing;
[0448] a display located on or adjacent to the front surface of the housing; and
[0449] A covering substrate disposed on a display, wherein the covering substrate comprises the glass-based article of any one of embodiments 73-82.
[0450] Embodiment 84, a glass-based article comprising:
[0451] The stress distribution includes the CS region and the CT region, wherein the CT region is approximated by the following equation: Stress (x) = MaxT – (((CT n (n+1)) / 0.5 n )·|(x / t)-0.5| n ),
[0452] Where MaxT is the maximum tension value, CT n A positive value less than or equal to MaxT and in units of MPa is provided, x is the position along the thickness (t) in microns, and n is from 1.5 to 5.
[0453] Embodiment 85, a glass-based article as described in embodiment 84, wherein the CT region includes a maximum CT value of about 50 MPa to about 250 MPa, and the maximum CT value is located in a depth range of about 0.4·t to about 0.6·t.
[0454] Embodiment 86, a glass-based article as described in embodiment 84 or 85, wherein for a thickness in the range of about 0·t to about 0.1·t microns, the stress distribution includes a slope in the range of about 20 MPa / micron to about 200 MPa / micron.
[0455] Embodiment 87, a glass-based article as described in any of embodiments 84-86, wherein the stress distribution is approximated by multiple error functions measured from 0.5·t to the surface.
[0456] Embodiment 88, use of a glass substrate in a strengthened glass-based article, the glass substrate comprising (in mol %):
[0457] SiO2 in an amount of about 68 to about 75;
[0458] Al2O3 in an amount of about 10 to about 15;
[0459] B2O3 in an amount of about 0.5 to about 5;
[0460] Li2O in an amount ranging from about 2 to about 10;
[0461] Na2O in an amount ranging from about 0 to about 6;
[0462] MgO in an amount of about 1 to about 4;
[0463] ZnO in an amount from about 0 to about 3; and
[0464] CaO in an amount of about 0 to about 5,
[0465] wherein the glass substrate is ion-exchangeable and amorphous,
[0466] The glass substrate exhibits any one or more of the following:
[0467] A ratio of Li2O to R2O of about 0.45 to about 1;
[0468] The difference between the total amount of R2O and the amount of Al2O3 ranges from about -5 to about 0;
[0469] R ranging from about 0 to about 3 x The difference between the total amount of O (in mol %) and the amount of Al2O3; and
[0470] a ratio of the amount of MgO (in mole %) to the total amount of RO (in mole %) ranging from about 0 to about 1, and
[0471] The glass substrate is substantially free of nucleating agents.
[0472] Embodiment 89, a glass substrate comprising a composition comprising, in mol %,
[0473] SiO2 in an amount of about 68 to about 75;
[0474] Al2O3 in an amount of about 10 to about 15;
[0475] B2O3 in an amount of about 0.5 to about 5;
[0476] Li2O in an amount ranging from about 2 to about 10;
[0477] Na2O in an amount ranging from about 0 to about 6;
[0478] MgO in an amount of about 1 to about 4;
[0479] ZnO in an amount from about 0 to about 3; and
[0480] CaO in an amount of about 0 to about 5,
[0481] wherein the glass substrate is ion-exchangeable and amorphous,
[0482] The glass substrate exhibits any one or more of the following:
[0483] A ratio of Li2O to R2O of about 0.45 to about 1;
[0484] The difference between the total amount of R2O and the amount of Al2O3 ranges from about -5 to about 0;
[0485] R ranging from about 0 to about 3 x The difference between the total amount of O (in mol %) and the amount of Al2O3; and
[0486] a ratio of the amount of MgO (in mole %) to the total amount of RO (in mole %) ranging from about 0 to about 1, and
[0487] The glass substrate is substantially free of nucleating agents.
[0488] Embodiment 90, a glass substrate comprising a composition comprising, in mol %,
[0489] SiO2 in an amount of about 68 to about 75;
[0490] Al2O3 in an amount of about 10 to about 15;
[0491] B2O3 in an amount of about 0.5 to about 5;
[0492] Li2O in an amount ranging from about 2 to about 10;
[0493] Na2O in an amount ranging from about 0 to about 6;
[0494] MgO in an amount of about 1 to about 4;
[0495] ZnO in an amount from about 0 to about 3; and
[0496] CaO in an amount of about 0 to about 5,
[0497] wherein the glass substrate is amorphous and strengthened,
[0498] The Na2O concentration was varied and the glass substrate was essentially free of nucleating agents.
[0499] Embodiment 91, the glass substrate as described in embodiment 90, further exhibits any one or more of the following
[0500] A ratio of Li2O to R2O of about 0.45 to about 1;
[0501] The difference between the total amount of R2O and the amount of Al2O3 ranges from about -5 to about 0;
[0502] R ranging from about 0 to about 3 x The difference between the total amount of O (in mol %) and the amount of Al2O3; and
[0503] The ratio of the amount of MgO (in mol %) to the total amount of RO (in mol %) ranges from about 0 to about 1.
[0504] Embodiment 92, a glass-based article as described in any of embodiments 1-88, wherein the Knoop scratch threshold of at least one of the first surface and the second surface exceeds 7N.
[0505] Embodiment 93, a glass-based article as described in any of embodiments 1-88 and 92, wherein at least one of the first surface and the second surface has a Knoop scratch threshold of less than 14N.
[0506] Embodiment 94, a glass-based article as described in any of embodiments 1-88 and 92-93, wherein the strengthened glass-based substrate has one of the following: (i) at least 60% survival rate; (ii) at least 80% survival rate; when subjected to an inverted ball drop test using a 4.2g stainless steel ball with a diameter of 10mm dropped from a height of one of (i) about 80cm; (ii) about 88cm; (iii) about 90cm; and (iv) about 95cm onto 30-grit sandpaper arranged on the surface of the glass, there is a 100μm air gap between the sandpaper and the surface of the glass, wherein the survival rate is based on testing of at least 5 samples.
[0507] Embodiment 95, a glass-based article as described in any of embodiments 1-88 and 92-94, wherein the strengthened glass-based substrate has an average fracture height of one of: (i) greater than 70 cm; (ii) greater than 75 cm; (iii) greater than 80 cm; and (iv) greater than 85 cm; when subjected to an inverted ball drop test using a 4.2 g stainless steel ball with a diameter of 10 mm dropped onto 30 grit sandpaper arranged on the surface of the glass, there is a 100 μm air gap between the sandpaper and the surface of the glass, wherein the survival rate is based on testing of at least 5 samples.
[0508] This application also relates to the following items.
[0509] 1. Use of a glass substrate in a strengthened glass-based product, wherein the glass substrate comprises (mol %):
[0510] about 68 to about 75% SiO2;
[0511] About 10-15% Al2O3;
[0512] about 0.5 to about 5 of B2O3;
[0513] about 2 to about 10 Li2O;
[0514] about 0 to about 6 Na2O;
[0515] about 1 to about 4 of MgO;
[0516] about 0 to about 3 of ZnO; and
[0517] about 0 to about 5% CaO,
[0518] wherein the glass substrate is ion-exchangeable and amorphous,
[0519] The glass substrate exhibits one or more of the following properties:
[0520] The ratio of Li2O to R2O is about 0.45 to about 1;
[0521] The difference between the total content of R2O and the content of Al2O3 is from about -5 to about 0;
[0522] R x The difference between the total content (mol %) of O and the content of Al2O3 is from about 0 to about 3; and
[0523] The ratio of the content of MgO (mol%) to the total content of RO (mol%) is from about 0 to about 1, and
[0524] The glass substrate is substantially free of nucleating agents.
[0525] 2. A glass substrate comprising a composition comprising, in mol %:
[0526] about 68 to about 75% SiO2;
[0527] about 10 to about 15 of Al2O3;
[0528] about 0.5 to about 5 of B2O3;
[0529] about 2 to about 10 Li2O;
[0530] about 0 to about 6 Na2O;
[0531] about 1 to about 4 of MgO;
[0532] about 0 to about 3 of ZnO; and
[0533] about 0 to about 5% CaO,
[0534] wherein the glass substrate is ion exchangeable and amorphous,
[0535] Wherein the glass substrate exhibits one or more of the following properties:
[0536] The ratio of Li2O to R2O is about 0.45 to about 1;
[0537] The difference between the total content of R2O and the content of Al2O3 is about -5 to about 0;
[0538] R x The difference between the total content (mol %) of O and the content of Al2O3 is from about 0 to about 3; and
[0539] The ratio of the content of MgO (mol %) to the total content of RO (mol %) is from about 0 to about 1, and
[0540] The glass substrate is substantially free of nucleating agents.
[0541] 3. A glass substrate comprising a composition comprising, in mol %:
[0542] about 68 to about 75% SiO2;
[0543] about 10 to about 15 of Al2O3;
[0544] about 0.5 to about 5 of B2O3;
[0545] about 2 to about 10 Li2O;
[0546] about 0 to about 6 Na2O;
[0547] about 1 to about 4 of MgO;
[0548] about 0 to about 3 of ZnO; and
[0549] about 0 to about 5% CaO,
[0550] wherein the glass substrate is amorphous and strengthened,
[0551] The Na2O concentration varies, and the glass substrate is substantially free of nucleating agents.
[0552] 4. The glass substrate according to item 3, further exhibiting one or more of the following properties:
[0553] The ratio of Li2O to R2O is about 0.45 to about 1;
[0554] The difference between the total content of R2O and the content of Al2O3 is from about -5 to about 0;
[0555] R x The difference between the total content (mol %) of O and the content of Al2O3 is from about 0 to about 3; and
[0556] The ratio of the content (mol %) of MgO to the total content (mol %) of RO is about 0 to about 1.
[0557] 5. The glass-based article of any one of items 1-4, wherein at least one of the first surface and the second surface has a Knoop scratch threshold greater than 7N.
[0558] 6. The glass-based article of any one of items 1-5, wherein at least one of the first surface and the second surface has a Knoop scratch threshold of less than 14N.
[0559] 7. A glass-based article as described in any of items 1-6, wherein, when a 4.2 g stainless steel ball with a diameter of 10 mm is dropped from one of the following heights: (i) about 80 cm; (ii) about 88 cm; (iii) about 90 cm; and (iv) about 95 cm onto 30 grit sandpaper arranged on the surface of the glass for an inverted ball drop test, the strengthened glass-based substrate has one of the following survival rates: (i) at least 60% survival rate; (ii) at least 80% survival rate, with an air gap of 100 μm between the sandpaper and the glass surface, wherein the survival rate is based on testing of at least 5 samples.
[0560] 8. A glass-based article as described in any of items 1-7, wherein, when a 4.2 g stainless steel ball with a diameter of 10 mm is dropped onto 30 grit sandpaper arranged on the surface of the glass to perform an inverted ball drop test, the strengthened glass-based substrate has one of the following average fracture heights: (i) greater than 70 cm; (ii) greater than 75 cm; (iii) greater than 80 cm; and (iv) greater than 85 cm, with an air gap of 100 μm between the sandpaper and the glass surface, wherein the survival rate is based on testing of at least 5 samples.
Claims
1. A glass-based product comprising: 45 mol % to 75 mol % SiO2; 5 mol% to 20 mol% Al2O3; greater than 1 mol % to 6 mol % B2O3; 1 mol % to 8 mol % Na2O; 2 mol% to 10 mol% Li2O; Less than 3 mol% K2O; Up to 8 mol % of alkaline earth metals; Less than 1 mol% ZrO2, of which The ratio of Li2O to R2O is greater than 0.5 and wherein R2O is the total content of Na2O, Li2O and K2O, and the total amount of R2O is 5 mol% to 15 mol%.
2. The glass-based article of claim 1, wherein the glass-based article comprises: 0 mol % to 5 mol % MgO; and 0 mol % to 2 mol % ZnO.
3. The glass-based article of claim 1, wherein the glass-based article comprises: greater than 1 mol % to 4 mol % B2O3; 1 mol % to 4 mol % Na2O; 6 mol% to 10 mol% Li2O; Less than 1 mol% K2O; Up to 5 mol % of an alkaline earth metal; and Less than 0.5 mol % ZrO2.
4. The glass-based article of any one of claims 1 to 3, wherein the glass-based article is substantially free of TiO2 and Fe2O3.
5. The glass-based article of any one of claims 1 to 3, wherein the glass-based article comprises 0 mol % to 4 mol % P2O5.
6. The glass-based article of any one of claims 1 to 3, wherein the ratio of Li2O to R2O is greater than 0.
7.
7. The glass-based article of any one of claims 1 to 3, wherein the glass-based article is strengthened and has a surface compressive stress greater than 300 MPa.
8. The glass-based article of claim 7, wherein the glass-based article has a compression depth of 0.1·t or greater, wherein t is the thickness of the glass-based article.
9. The glass-based article of any one of claims 1 to 3, wherein the glass-based article has a Young's modulus of 70 GPa or greater.
10. The glass-based article of any one of claims 1 to 3, wherein the glass-based article comprises a crystalline structure.
Citation Information
Patent Citations
Method and apparatus for a downhole spectrometer based on electronically tunable optical filters
US20050099618A1
Methods and apparatus for forming a glass ribbon
US20150027169A1
Precision glass roll forming process and apparatus
US8713972B2
Systems and methods for measuring a profile characteristic of a glass sample
US8854623B2
Precision roll forming of textured sheet glass
US9003835B2
